Mexican Genders, Mexican Genres: Cinema, Television, and Streaming Since 2010 - Smith, Paul Julian (Boydell & Brewer, 2021)
Gender and the contemporary audio-visual landscape of Mexico.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

The Evolution of Black Women in Television: Mammies, Matriarchs and Mistresses - Cheers, Imani M. (Routledge, 2017)
This book seeks to interrogate the representation of Black women in television. Cheers explores how the increase of Black women in media ownership and creative executive roles (producers, showrunners, directors and writers) in the last 30 years affected the fundamental cultural shift in Black women’s representation on television, which in turn parallels the political, social, economic and cultural advancements of Black women in America from 1950 to 2016. She also examines Black women as a diverse television audience, discussing how they interact and respond to the constantly evolving television representation of their image and likeness, looking specifically at how social media is used as a tool of audience engagement.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Brown Girls Who don’t Need Saving: Social Media and the Role of ‘Possessive Investment’ in The Mindy Project and The Good Wife - Moorti, Sujata (Television for Women, 2016)
This poignant assertionby acclaimed actor Viola Davis, star of the series How to GetAway with Murder (ABC, 2014-), during her Emmy acceptance speechwent viral and becamethe flashpoint for heated discussion about contemporary television’s representational practices. The statement draws attention to questions of taste, what is acknowledgedby the industry and audiences as quality television and the political economy of thecontemporary industry. This moment in television history, with its attendant socialmedia afterlife, captures the key elements I wish to explore in this chapter: represen-tations of women of colour, production practices and viewer responses. As Viola Davisnotes in the quote above, the contemporary US television landscape offers limited rolesfor people of colour. The few shows starring people of colour have become the focus ofintense social media exchanges. In this chapter, I will explore how televisual womenof colour have become a key site from which viewers assert a possessive investmentof racialised identity. By focusing on social media responses, I delineate the ways inwhich viewers invest symbolic and literal ownership over these representations.Through such a multifaceted examination, this essay aims to elaborate how women ofcolour are accommodated within the concept of television for women, a term inter-rogated in this volume. In addition, I illustrate the ideological instability of the term‘women of colour’ and the capaciousness of the concept ‘television for women’.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Shaded Lives: African-American Women and Television - Smith-Shomade, Beretta E. (Rutgers University Press, 2002)
Since its invention, television has been one of the biggest influences on American culture. Through this medium, multiple visions and disparate voices have attempted to stake a place in viewer consumption. Yet even as this programming supposedly reflects characteristics of the general American populace, television-generated images are manipulated and contradictory, predicated by the various economic, political, and cultural forces placed upon it. In Shaded Lives, Beretta Smith-Shomade sets out to dissect images of the African American woman in television from the 1980s. She calls their depiction "binaristic," or split. African American women, although an essential part of television programming today, are still presented as distorted and deviant. By closely examining the television texts of African-American women in comedy, music video, television news and talk shows (Oprah Winfrey is highlighted), Smith-Shomade shows how these voices are represented, what forces may be at work in influencing these images, and what alternate ways of viewing might be available. Smith-Shomade offers critical examples of where the sexist and racist legacy of this country collide with the cultural strength of Black women in visual and real-lived culture. As the nation's climate of heightened racial divisiveness continues to relegate the representation of Black women to depravity and display, her study is not only useful, it is critical.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Real Housewives or Real Lies? New Constructions of "Housewives" on The Real Housewives of Atlanta - Shorter, Shavonne R. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
An old adage prescribed that “art imitates life.” If one believes this to be true, then it is plausible that entertainment is a source from which information about everyday life can be gleaned? Can U.S. television shows provide a looking glass into how Americans perform certain aspects of their lives? For a “real” look into how careers are performed, I have examined content from a reality television show which bears a title that implies something about the cast— the Bravo Network’s Real Housewives of Atlanta series. This show was chosen for two reasons. First, The Real Housewives of Atlanta is the most popular show among the “Housewives” franchise. Thus with each airing of the show, those who watch have the opportunity to learn more about the career aspirations, roles, and behaviors, of the cast members. Second, this is the only show within The Real Housewives franchise that features a primarily black cast. As such, the question emerges— can this show provide insight into the way black women construct their career roles? Another goal of this study is to determine how cast members construct notions of housewifery. Hence, throughout this chapter, readers will see that these women are not the typical “housewives,” rather they have reinvented what it means to be a housewife in the modern age.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The "Down Ass Bitch" in the Reality Television Show Love and Hip Hop: The Image of the Enduring Black Women and Her Unwavering Support of the Black Man - Alameen-Shavers, Antwanisha (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Within Spoken Soul, better known as Ebonics, the term down can be used as an adjective to describe a person that willingly yields a tremendous amount of support to another person. The “Down Ass Bitch” (DAB) is a controlling image of the black woman that calls for her unwavering support of the black man, even when it is pernicious to her best interest. In fact, we can see this in the black community on many levels: (1) from black women faithfully waiting years for men to be released from prison; (2) hiding domestic abuse or rape at the hands of black men for the sake of protecting the race; or (3) sexually exploiting our bodies for the financial benefit of black men. However, what is most interesting about this particular stereotype of the black woman being “down” for her man is that this is not an expectation that is asked of the black man. It is this author’s contention that the “Down Ass Bitch” is obsequious to the powers of black men— though she is portrayed as being strong, aggressive, and assertive. Essentially, the “Down Ass Bitch,” a highly celebrated image in the black community, is the black version of the submissive white woman, the Eurocentric construction of the idealized womanhood. Various controlling images of black womanhood— such as the mammy, the jezebel, and the welfare queen— served as justifications for the oppression of black women and have been discussed significantly by scholars.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Dehumanized and Empowered? Black Women, Reality Television, and Love and Hip Hop Atlanta - Bennett, Patrick; Griffin, Rachel Alicia (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
In recent years, scripted television has been joined by a more “realistic” look into peoples’ lives— reality television. Reality television claims to give viewers an unmediated glimpse into how real people live. The “realness” of reality television invokes controversy by providing a voyeuristic and potentially exploitive look into people’s lives. As the genre has matured, shows that offer insight into communities that are systemically underrepresented have become common. Indicative of this trend are shows that depict the lives of African Americans and opportunistically exploit representations of black culture for drama, ratings, and profit. One network that has taken considerable advantage of this is VH1— first, with the success of Flavor of Love and its spinoffs, then more recently with shows such as Basketball Wives and Love and Hip Hop. In fact, the excessive amount of fighting among Black women on Basketball Wives led to a boycott of the show, which prompted creator Shaunie O’Neal to promise less violence in its next season. Akin to Basketball Wives , Love and Hip Hop Atlanta exemplifies the trend of exploiting black culture. As members of the black community, we find ourselves both intrigued and troubled by the implications of the show. Capturing the essence of our paradoxical interpretation of Love and Hip Hop Atlanta — as one of many reality television shows that simultaneously reproduces and challenges negative stereotypes about blackness— are contradictory headlines such as “The 21 Most Ratchet Women of Black Reality TV,” “How Reality TV has Changed our Daughters,” and “Wealthy Reality Stars Humanize Black Women.”
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

A Critical Analysis of Black Womahood in NBC's The Apprentice - Griffin Padget, Donyale R.; Allison, Donnetrice C. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Reality programs rose to prominence based on claims that the shows depicted “real life,” but in recent years many shows have come under fire for being anything but “reality.” Orbe (1998) suggests viewers are drawn to such programs based on the notion that they show “real people in everyday interactions,” and there is a certain level of “unpredictability that comes with reality.” However, what has become predictable and potentially problematic, over the past two decades, are the negative stereotypes associated with African American women on these programs. This skewing of reality is particularly significant when we consider the limited opportunities these shows provide viewers to witness the many facets of black womanhood. From the head-bobbing and finger-waving of Alicia Calaway on season two of the hit show Survivor to the on-and-off-air mudslinging between Kenya Moore and NeNe Leakes of Real Housewives of Atlanta fame, black women are portrayed as disloyal, bitchy, lazy, difficult to work with, and a threat to others.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The "Tyra Tyrade": Reinforcing the Sapphire Through Online Parody - Patton, Tracey Owens; Snyder-Yuly, Julie (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Tyra Banks, supermodel and producer, is the creator of the reality show America’s Next Top Model ( ANTM ), which is now in its twenty-second cycle, and features contestants who present themselves to a panel of judges for modeling critique. ANTM has been nominated for twenty-nine awards, including the GLAAD Media Award and Image Award, and the show has received five awards in 2009 from the Teen Choice Award and the Director’s Guild of America Award. Further, ANTM is currently shown in over 120 countries. The winner of each cycle receives a featured spread in a magazine, a modeling contract with a prominent agency, and a $100,000 modeling contract from a cosmetics company. In 2005, however, there was an infamous episode— dubbed the “Tyra Tyrade,” —where Tyra Banks yelled at a contestant whom she had just eliminated from the show. This episode was parodied more than any other ANTM episode, with the penultimate parody shown on a 2007 episode of Family Guy (a primetime cartoon television show with millions of viewers each week), where Tyra turns into a lizard and eats the model. While this episode is now nine years old, parodies from as recently as 2014 continue to live on and, as we argue, perpetuate negative stereotypes of black womanhood, particularly as related to the Sapphire mediated stereotype— loud, bossy, angry black woman. From the various interpretations of the “Tyra Tyrade,” it is clear that those who created the parodies covertly and overtly ventured into maintaining white supremacist stereotypes of black womanhood— where one is supposed to be beautiful, a jezebel, or a mammy, but not a Sapphire. Continuing the marginalizing mediated tradition, in almost every parody, the Tyra character becomes the object of ridicule for being “excessively black” and outside the parameters of her hegemonically prescribed role, because she demonstrated negative emotions resulting in an assertion of her power as the expert.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Is She Strong or Just a B!@*#? Discussion of Black Women's Anger in the Reality Show Bad Girls Club - Goldman, Adria Y. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
It is near impossible to have a discussion of black women in reality television without mentioning the infamous Angry Black Woman (ABW). In fact, some critiques have argued reality television is damaging for black women since many shows focus heavily on this character. 1 This stereotypical characterization of black women is long-standing, due largely to its constant inclusion in media messages. As noted in chapter one, audiences were first officially introduced to her in the 1920s as Sapphire Stevens from the Amos ‘n’ Andy Show ; and her character continued to resurface throughout the years, across several different genres. Despite the many time periods through which this image has traveled, the key characteristic of the Sapphire— her unexplainable anger and aggression— seem to resonate in many modern day images of black women.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Can't Have It All: An Analysis of Black Motherhood on Reality Television - Alford, Allison M.; Maxwell, Madeline M.; Jones, Ryessia D.; Morris, Angelica N. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
In this chapter we analyze three reality TV (RTV) shows whose main characters do not fit the old movie stereotypes of dark-skinned maternal Mammies, bossy, brown Sapphires or light-skinned sexy Jezebels. Many RTV shows with black cast members are falling back on such stereotypical representations. In contrast, the female characters we analyze are smart and sophisticated, and they live in multi-racial environments. Hence, the primary mediarelated question we address concerns how one slice of black motherhood is represented. The social question we address concerns the extent to which the character presentations actually point to social progress, with diverse symbols and meaning making of real life, or are they as artificial and stereotypical— perhaps in new ways— as the old portrayals?
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Are Black Women Loud? Neoliberal and Postfeminist Protagonists in OWN's Televisual Sphere - Briceño, Mia E.; Estwick, Evene (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Jones’ comments reflect a general consensus among TV critics and viewers that: 1) the black women who command the most attention on reality television tend to portray stereotypical, Sapphire-like characters; 2) as audiences consume such portrayals, there is a consistent line of argument from producers that insists “pitting [black women] against each other” is expected or “what the people want;” and 3) black female reality TV stars are willing to indulge the Sapphire fantasy if it means they will be able to further a personal and/or professional agenda. These are important themes to interrogate, especially given the history of mass mediated representations of black Americans, as well as the present-day “evolution” of black characters and other characters of color on unscripted and scripted American television. However, because attention is primarily focused on arguably “negative” portrayals, there has not been much critical analysis of “alternative” or more nuanced portrayals of black women in the televisual sphere. This chapter represents an attempt to fill in some of that blank space by focusing attention on an underexplored and relatively new consortium of reality television programming that features black women who are defined by their roles as mothers and entrepreneurs.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

From 1990s Girl to Hip-Hop Wife: An Analysis of the Portrayal of Tiny as Black Mother in Reality Television - Jones, Ryessia D.; Jones, Johnny; Smith, Siobhan E. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Although African-American women are still underrepresented in narrative television, reality television appears to be a site where one can find many portrayals of them. As other scholars have explained, the representations of African American women in reality television are usually negative, generally presenting them as loud, angry, and without “class.” However, there has been little research on the complicated relationships of black motherhood, black wifehood, and their portrayals on reality television. One black mother who illustrates this tense interaction is Tameka “Tiny” Harris, nee Cottle, formerly of the 1990s girl group Xscape, and star of two reality television programs— BET’s Tiny & Toya , and VH1’s T.I. and Tiny: The Family Hustle . Though both programs prominently feature Cottle, BET’s program constructs Tiny as an emotionally strong and pragmatically capable business woman who maintains the emotional health and financial stability of her family while her relational partner/husband, rapper Tip “T.I.” Harris, is serving time in prison. However, upon T.I.’s return home, The Family Hustle presents Tiny as having little business savvy and as overly permissive with their blended family. This is a dangerous portrayal, given that reality TV purports to disseminate some version of “reality” to its viewers.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The God in Me: Faith, Reality TV, and Black Women - Egwu, Chetachi A. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
The display of spirituality, faith and religion is not a new phenomenon among black women in the United States, nor is it new to the world of media. Africans came to the Americas with their own sense of spirituality and religion, and the awareness of a higher being became the mortar that bound the community together during the trials of enslavement and subsequent oppression. Not surprisingly, this legacy of worship continues to provide solace and strength, with black women at the helm.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

High Tea, Church Hats, Pastor Wives, and Friendships: A Critical Race Feminism Analysis of Black Women in Preachers of L.A. - Whittington Cooper, Elizabeth (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
The premise of the show revolves around six preachers in the Los Angeles area. They each pastor churches ranging from 3,500– 4,000 members; however, one pastor’s church has nearly 20,000 members (season 1: episode 1). A multitude of cameras follow the stories of each of the pastors’ lives, their relationships with each other, as well as their wives relationships with one another. The show has five black male preachers and one white male preacher. In season 1, all of the pastors— except for two— are married; one of the unmarried pastors is engaged to the mother of his child, and the other has a long-standing relationship with a female friend who frequently appears on the show. As viewers watch the show, they are given a glimpse into the world of evangelical preachers. Although at first glance the show seems to only focus on the men, the women provide an interesting glimpse at what it means to be a preacher’s wife, fiancée, or female companion. There were a total of eight episodes that aired over the course of two months. This chapter explores how black women and their friendships are portrayed on Preachers of L.A. — including the one white woman on the show. It also examines their discourse between one another— using critical race feminism to analyze the roles of these women as first ladies (a term used to describe the wives of pastors), their relationship with one other, and the conversations they have surrounding sex, marriage, relationships, and friendships. The chapter focuses on the first season of the show, which began in the fall of 2013. The show was later renewed for a second season, which began airing late summer 2014. This critique attempts to bring awareness to black women in the church and the discourse that perpetuates the stereotypes of black women on television. It also aims to initiate further conversations on various stereotypes— regardless of context— that have the potential to bear negatively on black women.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Queering/Quaring Blackness in Noah’s Arc - Yep, Gust A.; Elia, John P. (Queer Popular Culture: Literature, Media, Film, and Television, 2007)
This chapter provides a description and critical analysis of Noah’s Arc , a Logo cable television series featuring a predominantly African American gay male cast. Queer theory and quare studies are used as theoretical tools to examine the conceptions of blackness in general, as well as representations of blackness in Noah’s Arc . Thereafter this chapter turns to an analysis of the representations in this series to illustrate how Noah’s Arc not only queers and quares notions of authentic blackness but also serves to expand various notions of blackness. Finally, this chapter provides a treatment of how whiteness and heteronormativity are implicated in this recent iteration of a racialized queer visibility in popular culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Graphic Blackness/Anime Noir: Aaron McGruder’s the Boondocks and the Adult Swim - Whaley, Deborah Elizabeth (Watching While Black, 2012)
Aaron McGruder’s “The Return of the King” (2006) is one of many of the artist’s controversial episodes, yet it stands out because of the criticism it received among mainstream media outlets and civil rights leaders. It was the ninth episode to air from his series The Boondocks, which is an anime show that airs on the Cartoon Network’s Adult Swim cable channel. McGruder presents the following scenario in “The Return of the King”: What if Martin Luther King Jr. (MLK) did not die after his April 4, 1968, shooting and instead awoke after being in a coma for thirty-two years?
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Nigger, Coon, Boy, Punk, Homo, Faggot, Black Man: Reconsidering Established Interpretations of Masculinity, Race, ans Sexuality Through Noah’s Arc - Cunningham, Mark D. (Watching While Black, 2012)
At best, our knowledge about the lives and experiences of Black gay men is limited to a series of stereotypes, snap judgments, and ridicule. In terms of television media product, this aforementioned knowledge has been packaged mostly within the framework of comedy: a red-leather-clad Eddie Murphy talking about the most effective ways to shield his ass from the gay male gaze in the 1983 HBO stand-up performance Delirious ; Damon Wayans and David Alan Grier’s effeminate film critics Blaine Edwards and Antoine Merriweather on the 1990s television variety show In Living Color ; fashionista panel members Miss J and Andre Leon Talley
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Prioritized: The Hip Hop (Re)Construction of Black Womanhood in Girlfriends and the Game - Lewis, Nghana (Watching While Black, 2012)
Why is it important that a Black woman created, wrote for, and co-produced¹ two highly-regarded television situation comedies that engaged a variety of Black women’s health issues while at the same time these issues were being reduced, simplified, or altogether ignored in mainstream American hip hop? Mara Brock Akil tacitly responded to this question when asked why four episodes of the third season of Girlfriends (2000–2008), the situation comedy she created and co-produced for UPN, addressed the HIV/AIDS crisis among Black women in America. “I have things I want to say,” explained Brock Akil, “about bridging television’s gap between
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Gimme a Break! and the Limits of the Modern Mammy - Fuller, Jennifer (Watching While Black, 2012)
Picture this: a comedy about an overweight Black woman who lives with and takes care of a white family. Joking all the way, she cooks, cleans, helps the father of the family, and comforts the children. Then at one point, we see the father holding his gun and pointing toward the door. The Black woman enters and jumps up and down, screaming, “Massa! Massa! Massa! Please don’t shoot!” It is easy to imagine these scenes in a 1930s film about the antebellum South. But they are actually from the first episode of a 1980s sitcom.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

‘Calling Out Around the World’: The Global Appeal of Reality Dance Formats - Heller, Dana (Global Television Formats: Understanding Television Across Borders, 2012)
In this chapter, I would like to consider how interactive reality television contributes to the negotiation between national particulars and transnational media ﬂows. Speciﬁcally, I want to look at the successful franchise So You Think You Can Dance , a dynamic global media ﬂashpoint and a remarkably adaptable format that serves as a site of pleasurable and contradictory engagement with the sense of national culture and community that television manufactures. But what makes the show of particular interest to me is that it allows audiences, in an increasing number of television markets around the world, to collectively determine their ideal national performers through a competition that requires mastery of a virtual international smorgasbord of popular dance forms and styles, the vast majority of which originate elsewhere, or from within the national, racial, and ethnic cultures of others. Second, in choosing to examine dance shows, I join with a growing number of scholars who have, over the past 15 years, argued for increased attention to dance as a primary site of knowledge production concerning bodies, identities, and representation.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Israël (corpus analysé); Proche-Orient (corpus analysé); Turquie (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Introduction: American Game Studies - Jagoda, Patrick; Malkowski, Jennifer (American Literature, 2022)
In 2017, the American game designer Momo Pixel released the single-player, browser-based game Hair Nah. In this game, you play as Aeva, a Black woman taking trips to locations that include Osaka, Havana, and the Santa Monica Pier. As you move through levels on your journey—taking a taxi ride, traversing airport security, sitting on an airplane—you must slap away increasingly aggressive white hands that reach into the frame to touch your hair. Though Hair Nah taps into the genre of a casual button-mashing game, this interactive experience also explores the topic of microaggressions via unwanted hair touching. If you slap away enough hands on your travels, you reach a screen welcoming you to your destination with the message “YOU WIN!” but the caveat, “The game is over, but this experience isn’t. This is an issue that black women face daily. So a note to those who do it STOP THAT SHIT.”
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

Reconsidering Lost Opportunities for Diverse Representation - Nguyen, Josef (American Literature, 2022)
This article considers the cultural politics of frustrated potential for diverse representation in games by examining developer comments on the 1995 digital game I Have No Mouth, and I Must Scream, adapted from Harlan Ellison’s 1967 science fiction story of the same name. While Ellison’s story featured a gay man named Benny among the protagonists, the game developers adapted Benny without his original sexual identity. In a 2012 Game Informer magazine article, however, the developers reflected on their version of Benny as a “lost opportunity” for exploring gay identity. Rooted in discussion of this frustrated potential for a gay in-game Benny, this article interrogates a logic of lost opportunity for diverse representation present in game-development discourse, which manifests in a longing for more diverse characters that could have been but never came to be. This logic suggests particular ways that developers might conceive of diverse representation as simply a design issue under neoliberal logics of economic opportunity, commercial risk, and fetishized innovation—without meaningful consideration of political significance. Opposing this instrumentalization of frustrated diverse representation, this article draws on queer game studies and speculative design and literature to explore the possible contours and implications of diverse characters that never were more seriously than such comments typically do. Doing so demands more than romanticized longings for lost opportunities for diverse representation that treat this longing as the end in itself.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Making Queer Asiatic Worlds: Performance and Racial Interaction in North American Visual Novels - Patterson, Christopher B. (American Literature, 2022)
This paper argues that video games expose the presumptions separating “Asian America” and “Asia” in the traditional senses of isolation, origination, and presumed distance. It does so by focusing on the most “Asiatic” genre of video games today, the North American visual novel, which offers a counterdiscourse to normative modes of play and attempts to offer utopic spaces to reflect upon the “real” genres of race and neo–Cold War geopolitics. Using theories of performance from Dorinne Kondo and others, the author shows how queer indie visual novels are primarily aspirational, in that they build queer, utopic, and seemingly anti-racist worlds through the Asiatic space of the visual novel form. In so doing, they also allow players to explore the Asiatic as a means of repairing the traumas and distances of American imperial cultures. The article analyzes four visual novels to make this argument: three by non-racially-identifying North American designers—Doki Doki Literature Club! (2017) by Dan Salvato, Analogue: A Hate Story (2012) by Christine Love, and Heaven Will Be Mine (2018) by Aevee Bee—and Butterfly Soup (2017), a game by the queer Asian/American designer Brianna Lei. If games make the boundaries of Asia and America irrelevant, visual novels explore this irrelevance through Asiatic irreverence.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

The Mystery of the Missing AIDS Crisis: A Comparative Reading of Caper in the Castro and Murder on Main Street - Ruberg, Bo (American Literature, 2022)
This article addresses the seeming absence of the HIV/AIDS pandemic in video games from the 1980s and 1990s, the height of the US AIDS crisis. As Adrienne Shaw and Christopher Persaud have noted, stories about HIV/AIDS were pervasive across American popular media during this period, which also represented a boom in video game development. However, documentation remains of only a handful of early video games that mention HIV/AIDS. This article argues that, far from being absent from video game history, HIV/AIDS and the US AIDS crisis were actually influential in shaping a number of the design elements and narrative genres that have become important to contemporary video games. Scholars like Cait McKinney have demonstrated how people living with HIV/AIDS in America played a crucial part in the evolution of internet technologies that now form the backbone of video games. Through a comparative reading of two games by C. M. Ralph, Caper in the Castro (1989) and Murder on Main Street (1989), this article demonstrates how HIV/AIDS has also manifested in the content and form of video games, even (and perhaps especially) when it seems absent. Derritt Mason has explained how Caper in the Castro, widely celebrated as the first LGBTQ video game, contains clear echoes of the AIDS crisis. Yet, as this article demonstrates, HIV/AIDS remains a powerful presence even in Murder on Main Street, Ralph’s “straight version” of the game. Together, these games offer a microcosm through which to explore larger tensions between HIV/AIDS and video games, with the AIDS crisis representing a key element of what Cody Mejeur has termed the “present absence of queerness in video games.”
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

Du « dix-neuf » au « nineteen ». Une étude comparative des versions québécoise francophone et canadienne anglophone de la série télévisée 19-2 - Boisvert, Stéfany (Canadian Journal of Film Studies/Revue Canadienne d'études cinématographiques, 2016)
Cet article propose une étude comparative de la première saison de la série policière québécoise primée 19-2 (Ici Radio-Canada Télé, 2011-2015) et de son adaptation canadienne anglophone (Bravo, 2014-). L’étude des deux séries 19-2 permet d’investiguer, à travers un exemple récent, le processus d’adaptation télévisuelle au Canada. Les similitudes narratives et esthétiques entre les deux séries sont tout d’abord brièvement présentées: l’histoire et les arcs narratifs sont quasi identiques, la plupart des personnages conservent les mêmes noms, sans compter que les stratégies narratives marquantes de cette œuvres ont été pour la plupart reproduites dans la nouvelle version. Ces deux œuvres, appréhendées en tant que « performances » distinctes, sont ensuite analysées à travers le prisme du genre. L’analyse de quelques scènes clés et arcs narratifs permettra de démontrer que ces deux productions sont très différentes en ce qui concerne leur construction narrative de masculinités télévisées – particulièrement leur négociation différentielle de conceptions hégémoniques des identités – et leur représentation des rapports hommes-femmes.
Keywords: 1-TV; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Canada (corpus analysé); Canada (lieu de production du savoir); _Nettoyé

From a Real Place and Real People: Interview with Mississippi Damned Writer/Director Tina Mabry - Moore, Marlon Rachquel (Black Camera, 2011)
Marlon Rachquel Moore interviews emerging independent filmmaker Tina Mabry about her southern upbringing, racial and sexual consciousness, and the joys and turbulence of bringing her first feature-length film, Mississippi Damned, to the silver screen. Mississippi Damned is based on Mabry's family and set in her hometown of Tupelo, Mississippi.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

"Just Because I'm a Lesbian Doesn't Mean I'm Evolved" The "Bad Queer" Women's Comedic Web Series - San Filippo, Maria (Velvet Light Trap, 2020)
The queer women's comedic web series that have flourished in the last decade, serving as launching pads for their creators, coincided with media-industry nichification's segmentation of a consumer population regarded by advertisers and content providers as one monolithic LGBTQ community. The series I examine-from The Slope, which premiered in 2010, to Strangers, released in 2017-voice their creators' and characters' marginalization from and even opposition to such an imagined community, through recourse to what I call a "bad queer" rhetorical practice, which uses ironic metacommentary to critique assimilationist values and tropes alongside queer identity policing. These series emerged, at least initially, as an alternative sphere of queer media production and a queer discursive mode that employs disidentification as a politicized strategy to challenge dominant LGBTQ scripts. Offering an irreverent alternative to mainstream and millennial LGBTQ cultural products, these "bad queer" web series express the plurality of the queer "community" and expose political contestations within its ranks, and in so doing serve as brand differentiation for a new generation of queer media producers.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

The Statue of a Doctor Who Experimented on Enslaved Women still Stands in Alabama. But now There’s also a Monument to His Victims. - Matchan, Linda (Washington Post, 2021)
Michelle Browder’s “The Mothers of Gynecology” remembers Black women who endured surgeries without anesthesia, or consent.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice noir.e; _Nettoyé

On How Queer Cinema Might Feel. - Quinlivan, Davina (Music, Sound, and the Moving Image, 2015)
Examines the soundscapes of Derek Jarman's film "Blue" (1993) and Isaac Julien's video installation 'True north' (2007), and the way they contribute to promoting embodied responses in the viewer. Draws on the writings of Luce Irigaray and Laura U. Marks to explore the relationship between haptic theory and queer spectatorship.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Paris is burning: Intersectionality in 90s Queer Cinema. - Brew, Tara (Film Matters, 2019)
The overlap of marginalised race and sexuality is highlighted in the 1990 documentary "Paris is burning" which depicts the life of New York's black and Latino drag queens. The author offers an analysis of the social circumstances that gave birth to this culture which originated in 1980s Harlem.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

New Queer Cinema 2.0?: Lesbian-focused Films and the Internet. - Beirne, Rebecca (Screen, 2014)
The Internet distribution of lesbian-focused films seen as an example of the ways in which independent producers and distributors are offering their films for sale on the web. Incl. a table comparing costs and number of films available across a range of legal and illegal sites.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

We are here but are we Queer?: Lesbian Filmmaking versus Queer Cinema Conference, London, 12 March 1994 - Florence, Penny (Screen, 1994)
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

Straight Skin, Gay Masks and Pretending to Be Gay on Screen - Padva, Gilad (Routledge, 2020)
Straight  Skin,  Gay  Masks  and  Pretending  to  Be  Gay  on  Screen  examines cinematic depictions  of  pretending-to-be-gay,  assessing  performances  that not only reflect heteronormative and explicitly homophobic attitudes, but also  offer  depictions  of  gay  selfhood with  more  nuanced  multidirectional identifications. The case of straight protagonists pretending to be gay on screen is the ideal context in which to study unanticipated progressivity and dissidence in regard to  cultural  construction  of  human sexualities  in  the  face  of  theatricalized epistemological collapse. Teasing apart the dynamics of depictions of both sexual  stability  and  fluidity  in  cinematic  images  of  men  pretending  to  be gay offers new insights into such salient issues as sexual vulnerability and dynamics  and  long-term  queer  visibility  in  a  politically  complicated  mass culture  which  is  mostly  produced  in  a  heteronormative  and  even  hostile cultural environment. Additionally, this book initially examines queer uses of sexuality masquerade in Alternate Gay World Cinema that allegorically features a world pretending to be gay, in which straights are harassed and persecuted, in order to expose the tragic consequences of sexual intolerance. Films  and  TV  series  examined  as  part  of  the  analysis  include  The  Gay Deceivers, Victor/Victoria, Happy Texas, William Friedkin’s Cruising and many other straight and gay screens. This  is  a  fascinating  and  important  study  relevant  to  students  and researchers in Film Studies, Media Studies, Gender Studies, Queer Studies, Sexuality Studies, Communication Studies and Cultural Studies.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Coquie Hughes: Urban Lesbian Filmmaker Introduction to Yvonne Welbon’s Interview with Coquie Hughes - Brody, Jennifer Devere (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Toni Morrison purportedly began her career as a novelist because she noticed a dearth of books about black women. As a result of this limitation, Morrison desired to write books “for people like [her], which is to say black people, curious people, demanding people—people who can’t be faked, people who don’t need to be patronized.”¹ Similarly the writer, director, and filmmaker Coquie Hughes (born Latasha Iva Hughes in Chicago in 1970) has produced narratives that feature an array of queer black women—“Girls Like Us” as she calls them in her web series—who are curious, demanding, flawed, and
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

The Circuitous Route of Presenting Black Butch: The Travels of Dee Rees’s Pariah - Declue, Jennifer (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
At the 2012 Golden Globe awards, during her acceptance speech for the Best Actress award for her performance in The Iron Lady (Phyllida Lloyd, 2012), Meryl Streep gave a shout-out to Adepero Oduye for her role as Alike in Dee Rees’s feature film Pariah (2011). The sentiment behind this esteemed acknowledgment was that brilliant performances in important independent films were overlooked and deserved recognition. Streep would go on to win the Best Actress Oscar for a her portrayal of Britain’s first woman prime minister, the a ultraconservative Margaret Thatcher.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Creating the World Anew: Black Lesbian Legacies and Queer Film Futures - Gumbs, Alexis Pauline (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Deeply grounded in the legacy of Black lesbian artists, writers, and filmmakers, current Black lesbian filmmakers are helping to build infrastructure for a transformed future using deeply interconnected methods to transform the whole world and (while we’re at it) the meaning of life. This chapter looks at two projects, the established and evolving Queer Women of Color Media Arts Project based in San Francisco and the emerging Queer Renaissance and Black Feminist Film School Project based in Durham, North Carolina, as examples of the robust future of Black lesbian filmmaking as a transformative community-building practice. The Queer Women of Color
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Narrating Our History: An Introduction - Harris, Thomas Allen (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Around 1994 or 1995 I came across a call for articles for an anthology to be published by the XII Black International Cinema , documenting ten years of the festival and associated activities, 1986– 95. The request asked for articles and film lists from an international and intercultural group of scholars and filmmakers, and I thought this was an opportunity to document the exciting and pioneering work that was being done by a community of emerging Black lesbian and gay film-and video makers at the time.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

The Book of Ruins and Desire: Interactive Mechatronic Sculpture - Jennings, Pamela L. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The interactive book is a term heard frequently in reference to early experiments in multimedia production. But how to translate the concept of the book into a medium that has no paper, no pages, remains a challenge. Is not a book an object one holds in one’s hands—the cover affected over time by the acids and oils perspiring from the user’s skin, pages turned down and yellowed, torn or marked up? Research could show that the notion of the traditional book has been challenged throughout history. But this challenge has been accelerated with the growing accessibility of new computer
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Construction of Computation and Desire: Introduction to Yvonne Welbon’s Interview with Pamela L. Jennings - Keeling, Kara (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Early in the following interview, Pamela Jennings explains to Yvonne Welbon that her work gradually expanded from an initial and abiding interest in street photography toward working with and through forms of computational media. Jennings equates her move toward what she describes as “computational-based creative expression” with her growing interest in multimedia throughout the early 1990s, and she uses the term multimedia as a way of marking her work in a variety of different media and her interest specifically in computational media because the formulation computational media was not available to her then. The compelling relationship Jennings narrates between her
Keywords: 1-Cinéma; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Producing Black Lesbian Media - Moore, Candace (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In interviews the comedian Wanda Sykes describes being a successful black, openly gay woman in Hollywood as akin to being a unicorn. Clearly Sykes is majestic. Yet her joke hinges on a bitter truth: the mainstream media industry grants few women, not to mention lesbians of color, access to power. Despite shifts in the cultural imaginary around civil rights, Hollywood continues to maintain an embarrassing lack of diversity in its labor force, especially at decision-making levels. To battle this long-standing reputation, studios have developed diversity-hiring programs.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

A Cosmic Demonstration of Shari Frilot’s Curatorial Practice - Rastegar, Roya (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Shari Frilot is a filmmaker and curator whose creative practice has been driven by sustained explorations of sexuality, technology, desire, cosmic and subatomic structures, mixed-raced identity, and chaos. She has often expressed her modus operandi in the following terms: “It’s impossible to see a cloud when you’re in the middle of it. You have to move outside of the cloud to really get a sense of it.” By continually shifting between the outside and inside of a given framework—whether institutional or personal—Frilot has developed keen modes of challenging conventional structures for understanding and engaging the moving image.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Shine Louise Houston: An Interstice of Her Own Making - Stallings, L. H. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
It is the twenty-first century, and there is a black lesbian director and producer making pornography! Porn, a genre of film and media that in the last quarter of the twentieth century many black feminist lesbians viewed as capable only of representing and manifesting violence, abuse, and shame. In this essay I examine one of the early works of the black lesbian filmmaker Shine Louise Houston, In Search of the Wild Kingdom (2007), to explore how and why we have arrived at what is a transition from Blues Legacies and Black Feminisms to Pink and White Productions, and from New
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stepping Out on Faith: Interview with Coquie Hughes - Welbon, Yvonne (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
I grew up on the West Side of Chicago, where it was infested with gangs and drugs and violence. But I was always the type of person that wanted to be better than my environment, and I was also the type of person that didn’t want people to underestimate me because of where I came from. And so I made up in my mind, even as a young child, that I wanted to be somebody. I love making movies. I’ve wanted to be who I am ever since I saw Sidney Lumet’s movie The Wiz (1978).
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Birth of a Notion: Toward Black, Gay, and Lesbian Imagery in Film and Video - Parkerson, Michelle (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In mainstream media, gays and lesbians of color are either woefully present or predictably absent. The litany of black gay and lesbian characters in Hollywood films and network television reads like its own form of blackface. They range from the burly, black “bulldagger” as whore house madam in the 1933 film The Emperor Jones (starring Paul Robeson) to the predatory lesbian vamp in Spike Lee’s 1983 She’s Gotta Have It ; from Eddie Murphy’s ultracamp Miss Thing hairdresser on NBC’s Saturday Night Live to the snap! queen duo on Fox TV’s In Living Color. These relentless stereo types are part of
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

“Invite Me In!”: Angela Robinson at Hollywood’s Threshold - White, Patricia (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In 2005 Angela Robinson released her spy spoof, D.E.B.S. (2004). Robinson first realized the project as the short film D.E.B.S. (2003) through a training program with POWER UP (Professional Organization of Women in Entertainment Reaching Up), the only 501(c)(3) nonprofit film production company and educational organization for women and the GLBTQ community. In 2005 she also became the second black woman and first black lesbian to direct a studio feature, the Disney film Herbie Fully Loaded starring Lindsay Lohan. This moment marked the beginning of the black lesbian media maker hyphenate as Angela Robinson moved to television and began working on The L Word as a writer, director, and eventually producer. Patricia White's essay in this section, "'Invite Me In!': Angela Robinson at the Hollywood Threshold," offers an in-depth exploration of her career trajectory.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stereotypy, Mammy, and Recovery in Cheryl Dunye’s The Watermelon Woman - Wimbley, Karin D. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The Mammy has been in our field of vision as a popular icon representing black womanhood for more than a century in literature, film, and television and in consumer and material culture.¹ Described as an asexual, rotund slave of older age whose sole responsibility is to take care of her master’s children, Mammy is a beloved character who represents all that is nurturing and maternal. She is dark-skinned and boisterous and thought to have mannish features such as large feet and hands. Mammy wears a large skirt, hiding her sex, and covers her nappy hair with a bandanna or handkerchief.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Embodied Female Experience Through the Lens of Imagination - Green, Sharon R. (Journal of Analytical Psychology, 2010)
In 1971, I made a film entitled Self Portrait of a Nude Model Turned Cinematographer in which I explore the objectifying ‘male’ gaze on my body in contrast to the subjective lived experience of my body. The film was a radical challenge to the gaze that objectifies woman – and thus imprisons her – which had hitherto dominated narrative cinema. Since the objectification of women has largely excluded us from the privileged phallogocentric discourses, in this paper I hope to bring into the psychoanalytic dialogue a woman's lived experience. I will approach this by exploring how remembering this film has become a personally transformative experience as I look back on it through the lens of postmodern and feminist discourses that have emerged since it was made. In addition, I will explore how this process of imaginatively looking back on an artistic creation to generate new discourses in the present is similar to the transformative process of analysis. Lastly, I will present a clinical example, where my embodied countertransference response to a patient's subjection to the objectifying male gaze opens space for a new discourse about her body to emerge.
Keywords: 1-Cinéma; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

A Few of My Favourite Things: The Feiticeiro/a as Foundation for ‘Pervert’ Characterisation - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
A non-foundationalist construct for the Feiticeiro/a character that assumes neither an essentialist nature nor a determinist set of activities is possible. This does not prescribe a ‘type’ of ‘pervert’ character, but instead delineates an epistemic framing for a Feiticeiro/a character. This chapter explores an etymologically based semiotic approach to character construction that accounts for a Derridean view that language is constituted by binary reciprocal delimitations and for a view of sex as a dereified expression of materialised instances of engagement by sexual subjects, in terms of which sexuality is rendered as an opened-outward and connected function. The chapter further deals with an approach based in an empathic engagement between audiences and Feiticeiro/a characters, which is apposite for audiences identifying with but not necessarily liking characters. The chapter closes the volume’s argument around how transgressive, sexually focused Feiticeiro/a characters might productively be constructed in terms other than of essences and determinist actions, but in terms of ‘meaning’ found in the points of connection between heterogeneous bodily surfaces.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Absenting Heteropatriarchal Discourses: The Invisible ‘Pervert’ - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
Conservative discourses remain powerful in contemporary life. These demonise the notion of sexual transgressiveness without helping to give a clear, value neutral definition of what ‘transgressive’ is. Screenwriters attempting to write it into characters are therefore likely to rely on psychiatric epistemologies for sexual ‘perversion’ as framings for subjectivity. Unfortunately, Freudian epistemologies of ‘perversion’ render the psychical subject as invisible through built-in determining comparative reference to heteropatriarchal norms and through distinctions between ‘non-pathological’ and ‘pathological’ definitions. This chapter explores the Freudian constructs that entrench this, together with post-structuralist foundations that might revise the constitution and role of the individual subject (and therefore of filmic characters as facsimiles of real people) as he/she relates to the material world as a physical entity, and as he/she manipulates the discourses to which he/she is subject.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Anthropologically Present ‘Perverts’: Re-instating the Feitiço as the Feiticeiro/a - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
A post-humanist lens is useful as a starting-point to remedy the absenting and invisibilising effects of sexological epistemologies for the purposes of conceiving a constitution of ‘pervert’ filmic characters, since certain strains of existential thinking have a meta-theoretical pliancy that is useful for reflecting the non-binary character of complex people beyond simple identity categories, across a range of types and styles of filmic products. If matched with a semiological approach such as that espoused by Barthes, it thereby becomes possible to manipulate signs in the form of character constructions to represent people as more than the sum of their parts and to contain deeper significations that are built into the fabric of their construction. This requires a deeper understanding of the semiotic notion of ‘semes’ as the foundation for character construction. To this end, this chapter explores how sexual ‘perversion’ as reflected in notion of the ‘feitiço’ might serve as a foundation for a new episteme for ‘perverse’ characters, as the Feiticeiro/a as ‘sorcerer/sorceress’.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Psychoanalytic Absence: Freudian Object-Focus and the Resultant ‘Pervert Sans-Corpus’ - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
The notion of ‘perversity’ suggests inherent transgressiveness. However, a focus on practices does not help identify who filmic characters are in ways that might inform a paradigm for character identity suitable for translation into a visual medium. Failing to achieve this clarity, ‘perverts’ often end up as ‘ambulatory objects’ at once imagined and defined by what is not present. This chapter engages how this manifests in the nineteenth-century sexological discourses that reflected perverse prurience in terms of assumptions that all entities might be empirically identifiable in the same way that material phenomena can be perceived by means of the senses, which is especially visible in the various incarnations of Freudian constructs of ‘fetishism’ that refuse personal agency through reliance on a range of psychodynamic constructs.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Rephrasing Character Action for the Feiticeiro/a: External Coherence Through Transactional Relations - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If character actions are not to be seen in deterministic ways, then an alternative framing should be considered on which writers might base constructs of complexity of action. This is possible if action itself is seen as an expression of relationality rather than as activity-as-substance. Looking at people in this way enables the behaviour of Feiticeiro/a characters to be seen as activities that are more than the actions of combinations of sexed bodies in physical spaces. This chapter explores a construct for action on this basis as it becomes possible by acknowledging in a construct of ‘doing’ the phenomenological notions of ‘being’ as a Feiticeiro/a form constituted by a hybrid of ‘object-discourse-nature-society’ characterised by networks of confluence. The chapter explores the notion of the Feiticeiro/a character in terms of an internal coherency, taking account of interactions and activities (as exhibited through their material form), ‘naturalness’, linearity of course of action and embodied notions of meaning-creation.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Recherche-création; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Rephrasing the Feitiço: A New Episteme for Perverse Characters - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
Interesting and challenging Hollywood-style films that centre on sexually transgressive characters are not easy to script. Many writers fail as a result of an over-valuation of image at the expense of psychologically complex and challenging subjectivity. A hook for exploring the nature of this phenomenon lies in the notion of ‘involving and disturbing’, with a focus on how films might represent it and how audiences might perceive it, and with attention paid to how characters might be constructed. The chapter expands on how this notion of audience engagement might engage with screenwriting as a design function, aimed to construct characters in visual terms yet through words rather than pictures. In addressing certain epistemic limitations to writing character complexity, an alternative epistemic framing for ‘perverse’ characters is considered in terms of characterological ‘is-ness’, philosophical constitution and behaviours and actions.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Feiticeiro/a as a Materially Identifiable Character: Subjectively Conceived Filmic Participants - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If the Feiticeiro/a character is to be seen as a structure rather than a substance, the nature of such a structure requires elaboration. If this paradigm is to be internally coherent, a relation of intertwined co-existence between characters and audiences should be built into the framing in ways that provide functional epistemic signposts for mechanisms to translate characters’ intrinsic complexity to these audiences. This chapter approaches this by accounting both for the particularly visual nature of the filmic medium and for how screenplays are not a visual medium themselves and are put to different uses than other forms of narrative writing, therefore requiring distinctive attributes. An orientational notion of relationship between medium and audience is suggested as a foundation for the structure of Feiticeiro/a characters in terms of the philosophical distinction between ‘being’ and ‘appearance’, on the basis of which decisions might be made as to which elements of the character’s constitution should be made apparent and which should either remain invisible or intentionally be obfuscated.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Internally Coherent Feiticeiro/a: A Structure not a Substance - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
The categories for ‘perversion’ in the World Health Organization’s ICD fail to describe people and their practices, thereby obscuring the remarkable singularity of individuals and diversity of groups. Instead, they prescribe heteronormative sexual behaviour, which is unhelpful as a foundation for the Feiticeiro/a character. This chapter explores an alternative epistemic construct, as becomes available in the notion of a focalising character, which reflects a ‘semic’ construct that negates the notion of a ‘pervert’ character as a substance, but instead embraces the notion of a Feiticeiro/a character as a structure. The chapter further explores the philosophical nature of this structure as it relates to the thematic elements of a narrative whilst engaging in believable activities in a material world. The chapter then suggests an approach to structure based in a phenomenological notion of the replacement of ‘substance’ with ‘form’/‘structure’ as the foundation of meaning.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Towards an Episteme for the Feiticeiro/a: Realism in Character Construction - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
An episteme for the Feiticeiro/a as a filmic character who is ‘perverse’ needs a form if it is to be useful to writers wanting to construct complex transgressive sexual characters. The beginnings of this framing are productively associated with the semiotic notion of ‘connotation’. This chapter explores what is meant by complexity in character construction and suggests a framing focused on character as an embodied being as a helpful starting-point for an episteme for characterological ‘perversion’. The chapter explores this as a non-foundationalist framing that transcends problematic Cartesian distinctions, concrete object materiality and woolly broad-stroke statements of a disembodied discursive constitution of social and personal experience.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Writing ‘Perverse’ Behaviour for the Feiticeiro/a: Revisioning the ICD Diagnostic Criteria - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If the Feiticeiro/a as a psychologically defined and complex character is to be seen as an embodied form/structure (not substance) that exists in dialectical relationships between self, other and discursive constructions of society, a clearer indication should be made about what kinds of behaviours or actions he/she should engage in. This chapter explores how psychiatric diagnostic criteria fail to provide assistance, despite professing to authoritatively mark stable, reliable and accurate epistemic boundaries to sexual activity. The chapter thereby addresses questions of the description of actions versus the demarcation of thoughts, objects, feelings and time as invisible and abstracted notions that are virtually the opposite of what is useful for an episteme for the Feiticeiro/a. It also approaches how the diagnostic criteria codify ‘perverse’ activity in determinist terms, thereby insidiously refusing an epistemic construct of action into which is built an acknowledgement of the behaviours of the Feiticeiro/a as a complex subjectivity.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Cinema's Queer Witness: Ira Sachs's Last Address and the Indifferent View - Rodness, Roshaya (CR: The New Centennial Review, 2019)
Roshaya Rodness is a senior doctoral candidate in the Department of English and Cultural Studies at McMaster University. Her dissertation addresses recent movements in queer theory with a special focus on cinema, poststructuralist ethics, and the nonhuman. She has published in Canadian Literature, Chiasma: A Site for Thought , and World Picture on topics that include contemporary film, indigenous authorship, postcontinental philosophy, and dream theories.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

Performing Resistance/Negotiating Sovereignty: Indigenous Women's Perofrmance Art in Canada - Taunton, Carla Jane (Queen's University, 2011)
Performing Resistance/ Negotiating Sovereignty: Indigenous Women’s Performance Art In Canada investigates the contemporary production of Indigenous performance and video art in Canada in terms of cultural continuance, survivance and resistance. Drawing on critical Indigenous methodology, which foregrounds the necessity of privileging multiple Indigenous systems of knowledge, it explores these themes through the lenses of storytelling, decolonization, activism, and agency. With specific reference to performances by Rebecca Belmore, Lori Blondeau, Cheryl L'Hirondelle, Skeena Reece and Dana Claxton, as well as others, it argues that Indigenous performance art should be understood in terms of i) its enduring relationship to activism and resistance ii) its ongoing use as a tool for interventions in colonially entrenched spaces, and iii) its longstanding role in maintaining self-determination and cultural sovereignty.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Embodying Sovereignty: Indigenous Women’s Performance Art in Canada - Taunton, Carla (Narratives Unfolding: National Art Histories in an Unfinished World, 2017)
Homi Bhabha’s pivotal 1994 book,The Location of Culture, begins with an epigraph from Heidegger’s “Building Dwelling Thinking”: “A boundary is not that at which something stops but, as the Greeks recognized, the boundary is that from whichsomething begins its presencing.” Cultural engagement, whether antagonistic or affiliative in nature, is produced performatively – not as a reflection of something that is given or set in stone, but as an ongoing process of negotiation.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Re-Inventing Art Practices: Indigenous Women Artists Building Community through Art and Activism in Rural and Remote Manitoba - Nagam, Julie (University of Manitoba, 2006)
his thesis documents and explores community-based and socially engaged art by Indigenous women artists. Their artwork is impacting and strengthening communities in Manitoba. The Thesis explores the use of dialogical aesthetics in performance and socially-engaged art by Indigenous women artists in rural and remote areas of Manitoba, and relates these aesthetics to the concept of activism through their art and relationship to their community. The aim of this research and this paper is to document, support and expose the work of a small pocket of Indigenous women artists in Manitoba who are acting as activists or social change agents based on their artwork. I have arrived at this conclusion first by their personal testimonies, second, by their art being socially conscious and lastly, by their art practices entrenched in the framework of dialogical aesthetics, community-based and site-specific ideologies.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

(Re)Mapping the Colonized Body: The Creative Interventions of Rebecca Belmore in the Cityscape. - Nagam, Julie (American Indian Culture and Research Journal, 2011)
The cityscape holds the memories of indigenous bones and bodies that resurrect a deep sense of place that exists in the landscape of the city of Toronto. This deep sense of place is part of a connection to the land and stories of place. In this article, the author bridges the creative work of Anishinaabe artist Rebecca Belmore with the living histories of the indigenous bodies and bones that are buried beneath the ground of the city of Toronto and the city of Vancouver. She argues that Belmore's artwork is part of the living archive that performs cultural memory and employs telling as part of an embodied experience and a political act. Belmore's performance work creates, records, and stores indigenous stories of place. This article uses the ideas of cultural theorists Katherine McKittrick, Mishuana Goeman, and Matthew Sparke. Each of these people brings a different element to theories of the body and space. This article also uses feminist geographers Alison Blunt and Gillian Rose's work in women's colonial geographies to unpack the affects of the map in colonial spaces and the colonial gaze. (Contains 4 figures and 50 notes.)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Dans toute son exubérance : Affirmation de soi et autoreprésentation chez Caroline Monnet - Marcoux, Gabrielle (Canadian Journal of Film Studies, 2020)
In this interview, multidisciplinary artist Caroline Monnet discusses how acts of critical self-representation open up new spaces for territorial, linguistic, and identity negotiations and affirmations for Indigenous creators. In this sense, Monnet expresses her desire to put forward exuberant, strong, and diverse representations of Indigenous women in order to counter pervasive rhetorical dynamics of victimhood conveyed by mass media and cinema. As she presents some of the visual and discursive techniques she develops through her films, installations, and photographic works, Monnet reflects on the constructive dialogues – as well as the moments of incommunicability – that emerge and fade within various spaces and contexts of creation and reception. She considers that her individual and collective creative projects fall within a pivotal period of self-determination for Indigenous artists; she thus provides a critical overview of current discourses of (re)concililation.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Les archives à l’épreuve du temps : les recadrements temporels des courts métrages de la série Souvenir - Huberman, Isabella (Canadian Journal of Film Studies, 2020)
This article examines how “colonial time” is called into question in two short films of the National Film Board of Canada’s series Souvenir, from 2015. The question of time lies at the heart of this series, for which the NFB commissioned contemporary Indigenous filmmakers to take up their archives of visual material on Indigenous peoples. The colonial temporal framework is at work in the vast archives of ethnographic and documentary film and photography on Indigenous peoples dating back to the early twentieth century, in which Indigenous people are often represented as part of “vanishing” cultures. Thus, in this article, I underscore the temporal interruptions that occur when ethnographic visual material of Indigenous peoples is put into the hands of contemporary Indigenous artists. I focus first on what it means to repurpose dehumanizing colonial archives and ask whether visual sovereignty is in fact possible within the archives. By analyzing the reappropriation of archival footage in the short films Mobilize by Caroline Monnet and Etlinisigu’niet (Bleed Down) by Jeff Barnaby, I elucidate how the filmmakers break with modes of colonial time through what I propose to call “reframings” that offer alternative ways of conceiving of time. By rehabilitating ethnographic images, these filmmakers refuse to project the material into the distant past and complicate the readability of Indigenous images in the archives, revealing how the reappropriation of old images can be just as powerful as the production of new ones.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le cinéma autochtone au Québec: de la représentation à la ré-appropriation - Bertrand, Karine (Contemporary French Civilization, 2019)
Cet article se penche sur les relations et collaborations récentes entre les cinéastes autochtones et québécois. Une brève exploration des représentations autochtones antérieures et du contexte contemporain de co-réalisation Québec/Autochtonie nous permet d’esquisser un portrait plus nuancé des nouvelles configurations transnationales du paysage cinématographique québécois. De même, les notions d’autochtonisation du médium, de souveraineté visuelle et de survivance nous aideront à mieux cerner les œuvres de fiction réalisées par des cinéastes autochtones, qui contribuent à l’enrichissement d’un cinéma qui propose de nouvelles façons d’habiter les territoires québécois/autochtones.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le collectif Arnait Video Productions et le cinéma engagé des femmes inuits: Guérison communautaire et mémoire culturelle - Bertrand, Karine (Canadian Review of Comparative Literature / Revue Canadienne de Littérature Comparée, 2017)
Marie-Hélène Cousineau, qui regroupe des femmes inuits de la communauté d’Igloolik, utilise la vidéo pour démontrer l’importance de la femme inuit dans le développement et la cohésion de l’unité sociale et familiale de l’Arctique (passé, présent et futur). Soulignant la spécificité culturelle des femmes d’Igloolik, ainsi que la portée universelle de questions reliées par exemple à la maternité, au pouvoir et au potentiel des femmes qui sont considérées comme des agents de changement sociétal participant à la transmission et au renouvellement de la connaissance traditionnelle, les cinéastes d’Arnait ont participé à des projets novateurs (telle que l’initiative Live from the Toundra) où les outils technologiques (Internet, blogues, capsules vidéos, radio, satellite) ont servis à établir des ponts entre les di érentes communautés du Nord."
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

L’œuvre documentaire d’Alanis Obomsawin et la voix des femmes autochtones. - Bertrand, Karine (De l'exclusion à la solidarité: regards intersectionnels sur les médias, 2020)
Résumé livre : "L’intersectionnalité, telle qu’élaborée par les féministes noires dans les années 1980, permet de réfléchir aux rapports de pouvoir dans leur complexe enchevêtrement. Au-delà d’un certain effet de mode, cette éthique est plus que jamais nécessaire pour comprendre le monde, à l’aube d’une décennie marquée par un virus ayant partout exacerbé la violence et les inégalités, et mis en évidence les systèmes de privilèges. Et qu’arrive-t-il lorsque l’on porte ce regard attentif sur les médias ? Les textes rassemblés dans cet ouvrage explorent avec aplomb les questions de l’inclusion et de l’exclusion médiatiques. Que décoder du traitement média réservé au port du hijab dans le sport, aux agressions sexuelles à l’endroit des femmes noires et autochtones, ou encore, de la place de la sourditude et des transidentités dans l’espace public? Un recueil qui amène son lot de réponses éclairantes et douloureuses, une rareté dans le paysage des études culturelles et médiatiques francophones."--Page 4 de la couverture
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Remembering Vancouver's Disappeared Women: Settler Colonialism and the Difficulty of Inheritance - Dean, Amber (University of Toronto Press, 2015)
"Between the late 1970s and the early 2000s, at least sixty-five women, many of them members of Indigenous communities, were found murdered or reported missing from Vancouver's Downtown Eastside. In a work driven by the urgency of this ongoing crisis, which extends across the country, Amber Dean offers a timely, critical analysis of the public representations, memorials, and activist strategies that brought the story of Vancouver's disappeared women to the attention of a wider public. Remembering Vancouver's Disappeared Women traces "what lives on" from the violent loss of so many women from the same neighborhood. Dean interrogates representations that aim to humanize the murdered or missing women, asking how these might inadvertently feed into the presumed dehumanization of sex work, Indigeneity, and living in the Downtown Eastside of Vancouver. Taking inspiration from Indigenous women's research, activism, and art, she challenges readers to reckon with our collective implication in the ongoing violence of settler colonialism and to accept responsibility for addressing its countless injustices
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Auto-histoires et représentations communautaires dans le cinéma des femmes autochtones - Bertrand, Karine (Canadian Journal of Film Studies, 2020)
In the last decade or so, cinema has revealed itself to be an ideal medium for the transfer and/or remediation of the spoken word as well as stories coming from oral tradition and Indigenous culture. Indeed, cinema is a place of expression which favours cyclical creativity and contributes to the decolonization of stereotyped images propagated by external voices that do not understand the subtleties of languages (real and symbolic) that are anchored in indigenous peoples’ cultural memory. By exploring indigenous cinema as practised by women of diverse nations, this piece demonstrates how cinema can induce the compression and dilation of time, to bring to the audience the fluidity of a story that has been reconfigured according to a new time and carried by spoken words that have chosen to either emancipate themselves from the image or to materialize themselves in it. Furthermore, this article illustrates how a new generation of Indigenous women use cinema to retrace and/or rewrite their personal narrative with the help of autobiographical or collective stories that travel back in time to fill in the blanks left by a fragile memory and to express their will to make peace with a difficult colonial past. Finally, the writings of Lee Maracle (I Am Woman, 1988) and Natasha Kanapé Fontaine (Manifeste Assi, 2014) are being brought forth to show how films such as Suckerfish (Lisa Jackson, 2004) Bithos (Elle-Máijá Tailfeathers, 2015) and Four Faces of the Moon (Amanda Strong, 2016) contribute to the individual and community healing of Indigenous peoples of Canada, through an aesthetic of reconciliation. The exploration of these works, therefore allows us to shed light on and better understand the roles/internal mechanisms of visual autobiographies in the larger context of reconciliation with individual and collective stories/memories.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Hearts of our People: Native Women Artists - Ahlberg Yohe, Jill; Greeves, Teri (University of Washington Press, 2019)
"Women have long been the creative force behind Native American art, yet their individual contributions have been largely unrecognized, instead treated as anonymous representations of entire cultures. 'Hearts of Our People: Native Women Artists' explores the artistic achievements of Native women and establishes their rightful place in the art world. This lavishly illustrated book, a companion to the landmark exhibition, includes works of art from antiquity to the present, made in a variety of media from textiles and beadwork to video and digital arts. It showcases more than 115 artists from the United States and Canada, spanning over one thousand years, to reveal the ingenuity and innovation fthat have always been foundational to the art of Native women."--Page 4 de la couverture.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; _Nettoyé

Les arts wendats au service de la diplomatie et de la traite - de Stecher, Annette (Recherches amérindiennes au Québec, 2014)
Cet article porte sur les oeuvres artisanales des femmes wendates du xix ₑ siècle dans le contexte plus large des traditions des arts visuels wendats. En plus des objets commerciaux, l’auteure présente des objets faits pour être utilisés lors d’occasions cérémonielles et rituelles spéciales, et qui avaient aussi une valeur importante dans la communauté. Ces deux catégories d’artisanat dévoilent la façon dont les femmes wendates adaptaient leurs traditions artistiques aux sphères économiques et diplomatiques du monde colonial, et ce avec grand succès. Ces arts ont aidé la communauté à conserver une vision du monde amérindienne et ont préservé des traditions culturelles qui se sont perpétuées d’une génération à l’autre, tout en intégrant des innovations créatives. Ils démontrent aussi le rôle diplomatique important joué par les oeuvres présentées aux dignitaires eurocanadiens et européens dans un contexte cérémoniel, afin d’établir et de maintenir des relations politiques et économiques harmonieuses.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

“Embodiment and Subjectivity”: Intersectional Black Feminist Curatorial Practices in Canada - Joachim, Joana (RACAR: revue d'art canadienne / Canadian Art Review, 2018)
Dans le contexte de l’héritage canadien de colonialisme et de profond racisme, les musées ont contribué à l’oppression des Noir.e.s, des communautés de couleur et des peuples autochtones en gardant le silence ou en supprimant certaines histoires sous prétexte d’« objectivité ». Cet article examine les pratiques commissariales de deux femmes noires canadiennes, Gaëtane Verna, directrice et conservatrice en chef de la galerie d’art contemporain The Power Plant, et Andrea Fatona, commissaire indépendante, afin de situer le commissariat critique à l’intérieur de perspectives afroféministes intersectionnelles. En conformité avec une base conceptuelle fondamentale de ce féminisme, je soutiens que ce qui rend l’acte commissarial « critique » est la reconnaissance non seulement de la position qu’une personne occupe dans la société, mais aussi de celles dont elle ne fait pas toujours l’expérience. En examinant les pratiques de ces deux femmes, je mets au jour une riche histoire de l’art et du commissariat des Noir.e.s au Canada.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Shelley Niro. Scotiabank Award. - Rice, Ryan; Nanibush, Wanda (Steidl Verlag, 2018)
Shelley Niro is widely known for her ability to explode myths, transgress boundaries and embody the ethos of her matriarchal culture in a wide variety of mediums including photography, installation, film and painting. Niro creates photographic series that emphasize the medium?s inherent capacity for narrative and representation. She pushes the limits of photography by incorporating Mohawk imagery, re-appropriating traditional stories such as Skywoman and The Peacemaker, and by focusing on contemporary subjects with wit, irony and campy humor. Niro marries portraiture, performance art and satire by having her subjects and herself perform for the camera in ways that gently invite audiences to rethink their beliefs and preconceptions about indigenous peoples and themselves. With compassion and deep insight, Niro opens up the fault lines and desires of gender, sexuality and culture to create images of freedom from the status quo in representation. Photography was a medium that helped subjugate indigenous peoples, but in Niro?s revolutionary hands it empowers
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Land and Beaded Identity: Shaping Art Histories of Indigenous Women of the Flatland - Robertson, Carmen (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Le territoire constitue une force déterminante dans la création artistique. Les prairies austères, notamment, exigent des artistes actuels comme de ceux qui les ont précédés une adaptation constante, déterminée par l'accès aux ressources et la nécessité de mobilité. Cet article s'intéresse à l'impact du territoire sur la pratique du perlage telle qu'exercée par les femmes autochtones. Il met en relation des exemples de perlage traditionnel conservés dans les collections muséales de la Saskatchewan avec les œuvres de trois artistes contemporaines autochtones des plaines, soit Ruth Cuthand, Judy Anderson et Katherine Boyer. La comparaison vise à mieux comprendre le processus intergénérationnel de transmission des pratiques ancestrales et ainsi révéler comment s'exprime le territoire dans les objets et œuvres ornés de perles, qui contribuent à façonner le récit des plaines.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Killing the Indian Maiden: Images of Native American Women in Film - Marubbio, M. Elise (UPSO - University Press of Kentucky E-Books, 2006)
Killing the Indian Maiden examines the fascinating and often disturbing portrayal of Native American women in film. M. Elise Marubbio examines the sacrificial role in which a young Native woman allies herself with a white male hero and dies as a result of that choice. In studying thirty-four Hollywood films from the silent period to the present, she draws upon theories of colonization, gender, race, and film studies to ground her analysis in broader historical and sociopolitical context and to help answer the question, "What does it mean to be an American?"
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

Femmes et violence de masse. - Myre, Nadia; Uzel, Jean-Philippe (Hors-série, 2018)
"Si tous les groupes humains sont touchés par la violence à grande échelle, les femmes la subissent sous des formes spécifiques, comme en témoignent les assassinats systémiques des femmes et des filles autochtones en Amérique du Nord et en Amérique latine, ou encore les nombreux conflits armés (Syrie, Lybie, Birmanie, entre autres) dans lesquels le viol est érigé en arme de guerre. Les deux phénomènes peuvent d'ailleurs se recouper puisque l'un des tout premiers féminicides à avoir été qualifié et documenté comme tel en Amérique est celui ayant été perpétré contre les femmes mayas durant la guerre civile guatémaltèque au début des années 1980. Cependant, les femmes ne sont pas seulement les victimes de la violence de masse, puisqu'elles sont aussi les premières à témoigner et dénoncer pour faire barrage à cette violence. Ce numéro hors-série regroupe des articles et des projets visuels qui décrivent et analysent la violence de masse liée au genre. Il s'agit de réfléchir sur la manière de représenter cette violence et d'en témoigner, d'autant plus qu'elle est bien souvent rendue invisible et inaudible par le patriarcat, le colonialisme, les intérêts politiques en présence ou l'impéritie de l'État."
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Walking With Our Sisters: une commémoration artistique pour le féminicide autochtone, en marche vers la décolonisation - Bruneau, Julie (Recherches féministes, 2017)
En réaction au féminicide autochtone au Canada et à l’inertie du gouvernement canadien, des groupes militants, des associations de familles et de proches des disparues ainsi que des groupes de femmes autochtones lancent régulièrement des actions commémoratives diverses. L’auteure a mené une enquête ethnographique lors de l’installation artistique commémorative Walking With Our Sisters présentée à Ottawa en 2015, projet réalisé par l’artiste métisse Christi Belcourt. Ainsi, l’auteure s’est interrogée sur la valorisation des femmes autochtones et leur prise de pouvoir au travers de ce processus. Elle remet en question la définition du féminisme occidental en prenant en considération les critiques formulées par les féministes autochtones
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La conscience de la Mestiza. Vers une nouvelle conscience - Anzaldúa, Gloria (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2011)
Gloria Anzaldúa a délibérément écrit certains mots et certaines phrases en espagnol-chicano tout au long de cet article, choisissant pour des raisons politiques et esthétiques de produire un texte qui s’adresse à tout le monde mais peut être compris à des niveaux différents. Elle travaille ainsi aussi bien avec l’intelligibilité qu’avec la non-intelligibilité, liées au vécu et au positionnement social de chacun-e, au-delà de la langue elle-même. Pour tenter de respecter ce travail sur l’intelligibilité, nous avons procédé de la manière suivante. Dans certains cas, Anzaldúa a écrit une expression en espagno-chicano puis l’a traduite en anglais, nous avons alors procédé de la même manière. Dans les autres cas, nous avons laissé tel quel dans le corps du texte, ce qu’Anzaldúa a écrit en espagnol-chicano. Cependant, pour placer cette langue sur le même plan d’intelligibilité que l’anglais, pour le lectorat francophone, nous en proposons une traduction, en note. Enfin, nous avons ajouté un certain nombre de notes de contextualisation. Ainsi, les notes en lettres correspondent aux notes originales d’Anzaldúa, tandis que les notes en chiffres correspondent à la traduction de l’espagnol-chicano vers le français et enfin, les notes en i, ii, iii etc, correspondent aux notes des traductrices. Par ailleurs, deux termes sont particulièrement délicats à traduire : « raza » et « mestiza ». Au Mexique, le mot « raza » est polysémique. Au sens strict, il signifie « race », cependant son emploi actuel et courant n’implique aucune connotation raciale, mais plutôt populaire et affective (ma bande, mon quartier, ma famille élargie, les gens avec qui je m’identifie…), ce qui conduirait à le traduire plutôt par « peuple ». Nous avons donc choisi des traductions contextualisées, utilisant « race » pour la pensée de Vasconcelos (prise dans les courants racialistes internationaux des années vingt), et « peuple » pour la pensée d’Anzaldúa elle-même (qui l’utilise dans un sens actuel et populaire). L’ensemble de son œuvre montre amplement le caractère non-essentialiste de sa pensée, ce qui nous conforte dans ce choix. Enfin, le concept de « mestiza » (ou « mestizo ») possède au Mexique des connotations complexes et contradictoires. Il désigne une personne dominant-e par rapport à l’Indien-ne, mais aussi une personne dominé-e par rapport aux gens d’origine espagnole-européenne. Simultanément, il constitue l’archétype (positif) de la nouvelle « race » forgée dans l’ancienne colonie européenne transfigurée par l’indépendance puis la révolution. Pour Anzaldúa, le mot possède toutes ces connotations, mais signifie également la pluralité à l’intérieur de chaque être humain. Nous avons donc choisi de ne pas traduire le concept de « mestiza », qu’elle-même a décidé d’utiliser en espagnol, son article visant précisément à expliquer le sens nouveau qu’elle donne à la « nouvelle métisse ».
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Présences, mémoires individuelles et plurielles comme dispositifs de construction dans le travail des créatrices autochtones - Pageot, Édith-Anne (Espace, 2018)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La crise d'Oka en récits: territoire, cinéma et littérature - St-Amand, Isabelle (Collection InterCulture, 2015)
La crise d'Oka marque un véritable moment de rupture dans lesrelatlons entre les premiers peuples et les colonies de peuplement. Dans les suites immédiates de l’échec de l’accord du lac Meech, ce long siège armé de 78 jours rend visible une présence autochtone que les sociétés québécoise et canadienne avaient imaginée évanouie. Àl’inverse, l’opposition à l’empiétement mis en œuvre à Kanehsatàke età Kahnawàke réactive une longue histolre de résistance au projet colonial d'appropriation des terres et d'effacement des peuples autochtones. Ce livre envisage la crise d'Oka, ou la résistance à Kanehsatàke, comme un espace de focalisatlon où se donne à voir larelation globale entre les peuples. Qu'est-ce que l'événement fait surgir, transforme et crée, dans la scénographie du siège, mais aussi dans les films documentaires et les récits littéraires, autochtones et allochtones? À l'heure où une nouvelle génération revient sur cette crise politique aux enjeux non résolus, ce livre ouvre un espace où entrent en relation et s'affrontent différents intérêts, connaissances et expressions relatifs à ce conflit territorial. Il engage une réflexion épistémologique essentielle à un processus de décolonisation aussi impératif qu'exigeant.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Nadia Myre, en[counter]s - Tougas, Colette; Couëlle, Marcia; Myre, Nadia (Éditions Art mûr, 2011)
Nadia Myre is a multidisciplinary artist whose work explores themes of language, culture, and memory, and who sources the culture of her Algonquin ancestors as a way of confronting contemporary realities. This monograph provides a comprehensive first look at this Montreal-based artist's remarkable career
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Entre-deux mondes: métissage, identité et histoire sur les traces de Sonia Robertson, Sylvie Paré et Rebecca Belmore, ou, Les parcours artistiques de trois femmes artistes autochtones, entre la mémoire et l'audace - Charce, Chloë (Université du Québec à Montréal, 2008)
Ce mémoire est globalement axé sur la légitimité de la notion d'identité dans les contextes postcolonial et postmoderne. Plus précisément, il porte sur le concept de métissage dans l'art actuel à l'heure de la mondialisation culturelle, lieu propice à un renouvellement de l'identité et de l'imaginaire pour les communautés des Premières Nations d'Amérique du Nord. Il est divisé en deux parties. Les deux premiers chapitres énoncent une perspective socio-ethnohistorique autour des notions d'identité et de métissage, alors que le troisième chapitre expose un point de vue analytique à partir d'un corpus d'oeuvres de trois femmes artistes autochtones du Québec et de l'Ontario s'exécutant sur la scène artistique contemporaine, soit Sonia Robertson, Sylvie Paré et Rebecca Belmore. Plus spécifiquement, le premier chapitre fait état des connaissances et des discours sur les définitions même d'identité et de métissage dans les contextes colonial / postcolonial et moderne / postmoderne. Par extension, je pose cette question concernant l'hybridité culturelle: s'agit-il d'un principe d'homogénéisation et d'essentialisation des cultures ou d'un facteur garant d'hétérogénéité, favorable au mélange et aux échanges interculturels ? Le deuxième chapitre, quant à lui, énonce les contextes de dépossession territoriale et d'exiguïté culturelle dans lesquels ont été contraints les peuples des Premières Nations depuis l'époque coloniale. Il fait aussi mention des métissages artistiques (post)postmodernes, qui contribuent à un renouveau de l'imaginaire amérindien. Dans un esprit à la fois de contestation face à l'image folklorisée de l'« Indien » et de transmission des valeurs traditionnelles, les artistes autochtones font place à la réappropriation culturelle. Enfin, le troisième chapitre souligne les parcours identitaires de Sonia Robertson (Ilnue), Sylvie Paré (métisse huronne-wendat) et Rebecca Belmore (Anishinabekwe). À titre de comparaison, j'analyse un corpus d'installations et de performances sous le thème de la mémoire et de l'identité en lien avec les concepts élaborés dans les chapitres précédents. Le choix d'examiner le travail de trois femmes artistes provenant de communautés différentes permet de rendre compte de réflexions personnelles de la part de femmes autochtones face à la culture dominante et par rapport à leur culture d'origine. Ce choix vise par ailleurs à circonscrire, au sein même de leur production, l'importance de la tradition en fonction de leur affirmation identitaire. Je souhaite ainsi étudier comment ces propositions se positionnent dans un contexte de déterritorialisation culturelle en fonction d'une réalité post(néo)colonialiste, corrélative d'un entre-deux mondes. Pour conclure, je reviens sur les questions d'identité, de mémoire et de territoire en soulignant l'importance idéologique du combat identitaire des communautés autochtones, qui vise la mise en échec des préjugés et des constructions mythiques persistantes entre le « Blanc » et l' « Indien ». Je mesure en ce sens l'impact que pourrait avoir la pensée universelle amérindienne sur nos sociétés hypermodernes en crise et en quête de valeurs.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Numéro spécial : Cinémas et médias autochtones dans les Amériques : récits, communautés et souverainetés - Dudemaine, André; Marcoux, Gabrielle; St-Amand, Isabelle (Canadian Journal of Film Studies, 2020)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Queering Decolonization – Two Spirit Resistance Across Borders From Turtle Island to Palestine (2019)
Avec Alex Wilson, Jeffrey McNeil, Teddy Syrette, May Ela and Ahmed Maswadeh.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Two-Spirit Resistance - Mcneil-Saymour, Jeffrey (Whose Land is it anyway? A Manual for Decolonization., 2017)
The publication of Whose Land Is It Anyway? A Manual for Decolonization is inspired by a 2016 speaking tour by Arthur Manuel, less than a year before his untimely passing in January 2017. The handbook provides a variety of Indigenous perspectives on the history of colonialism, current Indigenous activism and resistance, and outlines the path forward to reconciliation
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice autochtone; _Nettoyé

Interpellations: Three Essays on Kent Monkman - Thériault, Michèle (Galerie Leonard & Bina Ellen art gallery, 2012)
Trois essais de Richard W. Hill, Jonathan D Katz et Todd B Porterfield.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; _Nettoyé

La danse au berdache de Kent Monkman - Sioui Durand, Guy (Inter, 2009)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; _Nettoyé

Éros et tabou: sexualité et genre chez les Amérindiens et les Inuit - Havard, Gilles; Laugrand, Frédéric (Septentrion, 2014)
Éros et tabou analyse les pratiques érotiques et les relations de genre au sein de diverses populations autochtones d'Amérique du Nord. Ces sociétés sont-elles plus ouvertes au principe de plaisir et aux pulsions sexuelles que les sociétés occidentales? L'ouvrage se penche particulièrement sur la tension existant parmi les Amérindiens et les Inuit entre, d'un côté, une sexualité d'apparence permissive qui peut acquérir un caractère public et décomplexé et, de l'autre, des pratiques strictement codifiées, souvent associées à des interdits. Le sexe apparaît donc comme un élément révélateur du social. Plusieurs thématiques sont examinées dans cette perspective, dont la différenciation des sexes et le travestissement, la contrainte et le consentement dans les unions et les mariages, la place du sexe dans la langue et la pensée symbolique, les relations sexuelles entre femmes autochtones et hommes d'origine européenne depuis le XVIe siècle ou encore la part jouée par les missionnaires dans la confrontation des Européens avec les moeurs autochtones. L'ouvrage est publié en hommage à Denys Delâge. Avec la collaboration de Marie-Pierre Bousquet, Denys Delâge, Raymond J. DeMallie, Louis-Jacques Dorais, Claude Gélinas, Anny Morissette, Murielle Nagy, Douglas R. Parks, Bernard Saladin d'Anglure et Olivier Servais.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Queer Latinidad: Identity Practices, Discursive Spaces - Rodriguez, Juana Maria (New York University Press, 2003)
According to the 2000 census, Latinos/as have become the largest ethnic minority group in the United States. Images of Latinos and Latinas in mainstream news and in popular culture suggest a Latin Explosion at center stage, yet the topic of queer identity in relation to Latino/a America remains under examined. Juana María Rodríguez attempts to rectify this dearth of scholarship in Queer Latinidad: Identity Practices, Discursive Spaces, by documenting the ways in which identities are transformed by encounters with language, the law, culture, and public policy. She identifies three key areas as the project’s case studies: activism, primarily HIV prevention; immigration law; and cyberspace. In each, Rodríguez theorizes the ways queer Latino/a identities are enabled or constrained, melding several theoretical and methodological approaches to argue that these sites are complex and dynamic social fields. As she moves the reader from one disciplinary location to the other, Rodríguez reveals the seams of her own academic engagement with queer latinidad. This deftly crafted work represents a dynamic and innovative approach to the study of identity formation and representation, making a vital contribution to a new reformulation of gender and sexuality studies.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Sexual Futures, Queer Gestures, and Other Latina Longings - Rodriguez, Juana Maria (New York University Press, 2014)
"Sexual Futures, Queer Gestures and Other Latina Longings proposes a theory of sexual politics that works in the interstices between radical queer desires and the urgency of transforming public policy, between utopian longings and everyday failures. Considering the ways in which bodily movement is assigned cultural meaning, Juana Maria Rodriguez takes the stereotypes of the hyperbolically gestural queer Latina femme body as a starting point from which to discuss how gestures and forms of embodiment inform sexual pleasures and practices in the social realm. Centered on the sexuality of racialized queer female subjects, the book's varied archive--which includes burlesque border crossings, daddy play, pornography, sodomy laws, and sovereignty claims--seeks to bring to the fore alternative sexual practices and machinations that exist outside the sightlines of mainstream cosmopolitan gay male culture. Situating articulations of sexual subjectivity between the interpretive poles of law and performance, Rodriguez argues that forms of agency continually mediate among these various structures of legibility--the rigid confines of the law and the imaginative possibilities of the performative. She reads the strategies of Puerto Rican activists working toward self-determination alongside sexual performances on stage, in commercial pornography, in multi-media installations, on the dance floor, and in the bedroom. Rodriguez examines not only how projections of racialized sex erupt onto various discursive mediums but also how the confluence of racial and gendered anxieties seeps into the gestures and utterances of sexual acts, kinship structures, and activist practices. Ultimately, Sexual Futures, Queer Gestures, and Other Latina Longings reveals--in lyrical style and explicit detail--how sex has been deployed in contemporary queer communities in order to radically reconceptualize sexual politics"--
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Metamorphic and Sensuous Brown Bodies: Queer Latina/x Visual and Performance Cultures in San Francisco Strip Clubs, 1960s–1970s - Otálvaro-Hormillosa, Gigi (Latin American and Latinx Visual Culture, 2019)
In the 1960s, topless entertainment became legal in San Francisco, although cross-dressing continued to be criminalized. This article documents queer Latina/x visual and performance cultures of San Francisco’s strip club industry during this critical moment. It employs visual and performance analyses that draw from ethnographic interviews and archival research about three Latinas who performed as exotic dancers during this period, two of whom were out transsexuals: Roxanne Lorraine Alegria, Vicki Starr, and Lola Raquel. Engaging Marcia Ochoa’s notion of “spectacular femininities” and Juana María Rodríguez’s theory of “queer gesture,” the article maps out a queer Latina/x herstoriography about the early days of topless entertainment in San Francisco. It demonstrates how the transgressive practices of these Latina performers enrich genealogies of queer and Latina/x performance and visual cultures since the 1960s. It thus contributes to the expansion and intersection of the fields of performance studies, Latina/x studies, and feminist, gender, and sexuality studies. These fields and their intertwinings offer critical tools to resist the sexism, homophobia, racism, transphobia, and whorephobia that pervade every level of society, as well as the cultural amnesia to which San Francisco has been increasingly prone due to its incessant gentrification and growing technocracy since the early 2010s.RESUMEN Este artículo documenta las culturas visuales y de performance latinas/x queer de los clubes de striptease de San Francisco durante un momento crítico en la historia de la ciudad. En la década de 1960, los shows en topless se legalizaron en San Francisco, aunque el travestismo se continuó criminalizando. Otálvaro-Hormillosa emplea análisis visuales y de performance que se basan en entrevistas etnográficas e investigación de archivo sobre tres latinas que actuaron como bailarinas exóticas durante este período, dos de las cuales reconocían públicamente que eran transexuales: Roxanne Lorraine Alegria, Vicki Starr y Lola Raquel. En diálogo con la noción de “feminidades espectaculares” de Marcia Ochoa y la teoría de “gestos queer” de Juana María Rodríguez, Otálvaro-Hormillosa describe una historiografía latina/x queer propiamente femenina sobre los primeros días del entretenimiento en topless en San Francisco. El artículo demuestra cómo las prácticas transgresoras de estas intérpretes latinas enriquecen las genealogías de las culturas visuales y de performance queer y latinas/x desde los años sesenta. Al hacerlo, contribuye a la expansión e intersección de los campos de los estudios de performance, estudios latinas/x, y estudios feministas, de género y de sexualidad. Estos campos y sus entrecruzamientos pueden ofrecer herramientas críticas para resistir el sexismo, la homofobia, el racismo, la transfobia y la putafobia que permea todos los niveles de la sociedad, así como la amnesia cultural a la que San Francisco ha sido cada vez más propenso debido a su incesante gentrificación y creciente tecnocracia desde principios de los años 2010.RESUMO Este artigo documenta a cultura visual e de performance na indústria de clubes de strip-tease de São Francisco, durante um momento crítico da história da cidade. Nos anos 60, o entretenimento topless se tornou legal em São Francisco, embora a prática do cross-dressing continuasse criminalizada. Otálvaro-Hormillosa emprega análise visual e de performance baseadas em entrevistas etnográficas e pesquisas de arquivos sobre três latinas que se apresentaram como dançarinas exóticas durante esse período, duas das quais eram transexuais: Roxanne Lorraine Alegria, Vicki Starr e Lola Raquel. Engajando a noção de “feminilidades espetaculares” de Marcia Ochoa e a teoria do “gesto queer” de Juana María Rodríguez, Otálvaro-Hormillosa mapeia uma herstoriografia queer latina/x sobre os sobre os primórdios do entretenimento topless em São Francisco. O artigo demonstra como as práticas transgressivas dessas artistas latinas enriquecem as genealogias das culturas visual e de performance queer e latina/x desde os anos 1960. Deste modo, contribui para a expansão e intersecção dos campos de estudos da performance, estudos latinos e estudos feministas, de gênero e sexualidade. Esses campos e seus entrelaçamentos podem oferecer ferramentas críticas para resistir ao sexismo, homofobia, racismo, transfobia e putafobia que permeiam todos os níveis da sociedade, bem como a amnésia cultural para a qual San Francisco tem sido cada vez mais propensa devido à sua gentrificação incessante e crescente tecnocracia desde o início dos anos 2010.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Interview with author, Dr. Laura Pérez - Ramirez, Abraham
Interview with author, Dr. Laura Pérez, Professor of Ethnic Studies at UC Berkeley on her most recent book, Eros Ideologies: Writings on Art, Sprituality, & the Decolonial.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Eros ideologies. Writings on art, spirituality, and the decolonial. - Perez, Laura E (Duke University Press, 2019)
In 'Eros Ideologies' Laura E. Perez explores the decolonial through Western and non-Western thought concerning personal and social well-being. Drawing upon Jungian, people-of-color, and spiritual psychology alongside non-Western spiritual philosophies of the interdependence of all life-forms, she writes of the decolonial as an ongoing project rooted in love as an ideology to frame respectful coexistence of social and cultural diversity. In readings of art that includes self-portraits by Frida Kahlo, Ana Mendieta, and Yreina D. Cervantez, the drawings and paintings of Chilean American artist Liliana Wilson, and Favianna Rodriguez's screen-printed images, Perez identifies art as one of the most valuable laboratories for creating, imagining, and experiencing new forms of decolonial thought. Such art expresses what Perez calls eros ideologies: understandings of social and natural reality that foreground the centrality of respect and care of self and others as the basis for a more democratic and responsible present and future. Employing a range of writing styles and voices-from the poetic to the scholarly-Perez shows how art can point to more just and loving ways of being.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Revista N'oj Panel on Decolonizing Aesthetics - Latinx Research Center (2020)
The Latinx Research Center's Revista N'oj hosted a round table discussion on Decolonial Aesthetics titled, "Decolonizing Art & Praxis in the Time of Covid-19." The talk included Jesus Barraza, Dr. Guisela Latorre, Dr. Mauricio Barros de Castro, and Dr. Laura E. Pérez. The panel was moderated by Revista N'oj editor, Abraham Ramirez.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Only Skin Deep: Changing Visions of the American Self - Fusco, Coco; Wallis, Brian (Abrams and International Center of Photography, 2003)
"By bringing together a provocative selection of essays and images, Only Skin Deep: Changing Visions of the American Self addresses the issues of nation, race, and selfhood and how they are depicted in ways that are challenging and informative, prompting readers to consider the impact of photography on our everyday lives." "If photographs are chiefly responsible for perpetuating myths of American identity, can a different reading of these representations break down distorting stereotypes? This is the central question posed by Only Skin Deep. The authors in this book forcefully argue that race and nation - and, indeed, photography itself - are fictions, cultural constructions that shape our social interactions. Even as symbols, these photographic depictions of ethnic difference and cultural superiority have very real consequences. This collection of works and essays addresses, for example, the lingering consequences of American colonial expansion; the conflict between public and private visualizations of individuals; the role of commercial imagery in shaping gender roles; the impact of fantasy in ethnic or ethnographic photography; and the uses of science to provide justification for politicized depictions of "race."" "Accompanying a major exhibition of the same name, Only Skin Deep offers a critical rereading of the archive of the history of photography. This applies to the works of famous photographers - such as Dorothea Lange, Walker Evans, Ansel Adams, and Edward Steichen - as well as lesser-known historical figures, including Charles Eisenmann, Frances Benjamin Johnston, Will Soule, and Toyo Miyatake. A substantial part of the book is devoted to contemporary artists and photographers who have moved beyond the multicultural approach to representations of "race" and have made an investigation of the semiotics of cultural identity a prevalent theme over the past decade. Among the recent photographers included are: Nancy Burson, Nikki S. Lee, Glenn Ligon, Paul Pfeiffer, Hulleah Tsinhnahjinnie, Cindy Sherman, Lorna Simpson, and Andres Serrano."--(BOOK JACKET)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Ain't I a Woman Black Women and Feminism - hooks, bell (Routledge, 2015)
This landmark work of history and theory challenges every accepted notion about the nature of black women’s lives. Ain’t I A Woman examines the impact of sexism on black women during slavery, the historic devaluation of black womanhood, black male sexism, racism within the recent women’s movement, and black women’s involvement with feminism. hooks refutes the antifeminist claim that black women are not victims of sexist oppression nor in need of an autonomous women’s movement. She pushes feminist dialogue to new limits by claiming that all progressive struggles are significant only when they take place within a broadly defined feminist movement which takes as its starting point that race, class, and sex are immutable facts of human existence. bell hooks’ insight as a black woman and a feminist extends the scope of feminist theory and practice for us all, and marks the emergence of a revitalized feminism in the 1980s.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Black Looks: Race and Representation - hooks, bell (Routledge, 2015)
"In the critical essays collected in Black Looks, bell hooks interrogates old narratives and argues for alternative ways to look at blackness, black subjectivity, and whiteness. Her focus is on spectatorship--in particular, the way blackness and black people are experienced in literature, music, television, and especially film--and her aim is to create a radical intervention into the way we talk about race and representation. As she describes: 'The essays in Black Looks are meant to challenge and unsettle, to disrupt and subvert.' As students, scholars, activists, intellectuals, and any other readers who have engaged with the book since its original release in 1992 can attest, that's exactly what these pieces do"(Provided by publisher)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

The Routledge Companion to Media and Race - Campbell, Christopher (Routledge Companions, 2017)
"The Routledge Companion to Media and Race serves as a comprehensive guide for scholars, students, and media professionals who seek to understand the key debates about the impact of media messages on racial attitudes and understanding. Broad in scope and richly presented from a diversity of perspectives, the book is divided into three sections: first, it summarizes the theoretical approaches that scholars have adopted to analyze the complexities of media messages about race and ethnicity, from the notion of 'representation' to more recent concepts like Critical Race Theory. Second, the book reviews studies related to a variety of media, including film, television, print media, social media, music, and video games. Finally, contributors present a broad summary of media issues related to specific races and ethnicities and describe the relationship of the study of race to the study of gender and sexuality"--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Examining the Intersection of Race and Gender in Video Game Advertising - Behm-Morawitz, Elizabeth (Journal of Marketing Communications, 2017)
Women and racial/ethnic minorities account for a growing percentage of video game players in the USA. The economic future of the video game industry may, in part, depend on the industry's ability to adapt marketing efforts to appeal to the growing female and racial/ethnic markets. Contrary to these efforts, however, is advertisers' reliance on stereotypes in advertisements to quickly establish a common understanding and wide appeal to a mass audience. This study investigates how race and gender intersect in the stereotypical character depictions used to market video games to consumers. A systematic content analysis was carried out of 383 US magazine advertisements of console, mobile, and PC video games. Stereotyping and intersectionality literatures were used as theoretical guides for this research. Findings reveal that the marketing of video games in the USA upholds some longstanding media stereotypes of minorities and women, including that of the White male hero, submissive sexualized female, Asian ninja, and deviant Black male. The potential social and economic implications of the video game industry's reliance on character stereotypes for the marketing of video games are discussed.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Exploring the Difficulties African-American Middle School Girls Face Enacting Computational Algorithmic Thinking over three Years while Designing Games for Social Change - Thomas, Jakita O.; Rankin, Yolanda; Minor, Rachelle; Sun, Li (Computer Supported Cooperative Work, 2017)
Computational algorithmic thinking (CAT) is the ability to design, implement, and assess the implementation of algorithms to solve a range of problems. It involves identifying and understanding a problem, articulating an algorithm or set of algorithms in the form of a solution to the problem, implementing that solution in such a way that the solution solves the problem, and evaluating the solution based on some set of criteria. CAT is an important scaffolded on-ramp as students develop more advanced computational thinking capabilities and apply computational thinking to solve problems that are more constrained and require greater expertise. Supporting Computational Algorithmic Thinking (SCAT) is both a longitudinal between-subjects research project and a free enrichment program supporting and guiding African-American middle school girls over three years as they iteratively design a set of complex games for social change. This article explores Scholars' reflections about the difficulties they faced while using CAT capabilities as they engaged in collaborative game design for social change over those three years. We particularly focus on how these difficulties changed over the course of three years as well as new difficulties that emerged from year to year as Scholars become more expert game designers and computational algorithmic thinkers.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Exploring Collaborative Talk Among African-American Middle-School Girls in the Context of Game Design for Social Change - Thomas, Jakita O.; Rankin, Yolanda; Saunders, Quimeka (Journal of Computing Sciences in Colleges, 2019)
Computer Science education research establishes collaboration among students as a key component in learning, particularly its role in pair programming. Furthermore, research shows that girls, an underrepresented population in computing, benefit from collaborative learning environments, contributing to their persistence in CS. However, too few studies examine the role and benefits of collaborative learning, especially collaborative talk, among African-American girls in the context of complex tasks like designing video games for social change. In this exploratory study, we engage 4 dyads of African-American middle school girls in the task of designing a video game for social change, recording the dyads' conversations with their respective partners over an eight-week summer game design experience during the second year of what has now become a six-year study. Qualitative analysis of dyadic collaborative discussion reveals how collaborative talk evolves over time in African-American middle-school girls.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Race and Media: Critical Approaches - Lopez, Lori Kido (New York University Press, 2020)
1. Racism and Mainstream Media / Lori Kido Lopez -- 2. Image Analysis and Televisual Latinos / Mary Beltrán -- 3. Visualizing Mixed Race and Genetics / Meshell Sturgis and Ralina L. Joseph -- 4. Listening to Racial Injustice / Dolores Inés Casillas and Jennifer Lynn Stoever -- 5. Branding Athlete Activism / Jason Kido Lopez -- 6. The Burden of Representation in Asian American Television / Peter X. Feng -- 7. Indigenous Video Games / Jacqueline Land -- 8. Applying Latina/o Critical Communication Theory to Anti-Blackness / Mari Castañeda -- 9. Asian American Independent Media / Jun Okada -- 10. Remediating Trans Visuality / Amy Villarejo -- 11. Intersectional Distribution / Aymar Jean Christian -- 12. Podcasting Blackness / Sarah Florini -- 13. Black Twitter as Semi-Enclave / Raven Maragh-Lloyd -- 14. Arab Americans and Participatory Culture / Sulafa Zidani -- 15. Diaspora and Digital Media / Lia Wolock -- 16. Disrupting News Media / Meredith D. Clark -- 17. Latinx Audiences as Mosaic / Jillian M. Báez -- 18. Media Activism in the Red Power Movement / Miranda J. Brady -- 19. Black Gamers' Resistance / Kishonna L. Gray -- 20. Cosmopolitan Fan Activism / Susan Noh.
Keywords: 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

On Video Games: the Visual Politics of Race, Gender and Space - Murray, Soraya (International library of visual culture ; 27, 2018)
Today over half of all American households own a dedicated game console and gaming industry profits trump those of the film industry worldwide. In this book, Soraya Murray moves past the technical discussions of games and offers a fresh and incisive look at their cultural dimensions. She critically explores blockbusters likeThe Last of Us, Metal Gear Solid, Spec Ops: The Line, Tomb Raider and Assassin's Creed to show how they are deeply entangled with American ideological positions and contemporary political, cultural and economic conflicts.As quintessential forms of visual material in the twenty-first century, mainstream games both mirror and spur larger societal fears, hopes and dreams, and even address complex struggles for recognition. This book examines both their elaborately constructed characters and densely layered worlds, whose social and environmental landscapes reflect ideas about gender, race, globalisation and urban life. In this emerging field of study, Murray provides novel theoretical approaches to discussing games and playable media as culture. Demonstrating that games are at the frontline of power relations, she reimagines how we see them - and more importantly how we understand them.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Video Games Have Always Been Queer. - Ruberg, Bonnie (New York University Press, 2019)
While popular discussions about queerness in video games often focus on big-name, mainstream games that feature LGBTQ characters, like 'Mass Effect' or 'Dragon Age', Bonnie Ruberg pushes the concept of queerness in games beyond a matter of representation, exploring how video games can be played, interpreted, and designed queerly, whether or not they include overtly LGBTQ content. 'Video Games Have Always Been Queer' argues that the medium of video games itself can-and should-be read queerly. In the first book dedicated to bridging game studies and queer theory, Ruberg resists the common, reductive narrative that games are only now becoming more diverse. Revealing what reading D.A. Miller can bring to the popular 2007 video game 'Portal', or what Eve Sedgwick offers 'Pong', Ruberg models the ways game worlds offer players the opportunity to explore queer experience, affect, and desire. As players attempt to 'pass' in 'Octodad' or explore the pleasure of failure in 'Burnout: Revenge', Ruberg asserts that, even within a dominant gaming culture that has proved to be openly hostile to those perceived as different, queer people have always belonged in video games-because video games have, in fact, always been queer.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Gaming at the Edge: Sexuality and Gender at the Margins of Gamer Culture - Shaw, Adrienne (University of Minnesota Press, 2015)
Video games have long been seen as the exclusive territory of young, heterosexual white males. In a media landscape dominated by such gamers, players who do not fit this mold, including women, people of color, and LGBT people, are often brutalized in forums and in public channels in online play. Discussion of representation of such groups in games has frequently been limited and cursory. In contrast, Gaming at the Edge builds on feminist, queer, and postcolonial theories of identity and draws on qualitative audience research methods to make sense of how representation comes to matter. In Gaming at the Edge, Adrienne Shaw argues that video game players experience race, gender, and sexuality concurrently. She asks: How do players identify with characters? How do they separate identification and interactivity? What is the role of fantasy in representation? What is the importance of understanding market logic? In addressing these questions Shaw reveals how representation comes to matter to participants and offers a perceptive consideration of the high stakes in politics of representation debates. Putting forth a framework for talking about representation, difference, and diversity in an era in which user-generated content, individualized media consumption, and the blurring of producer/consumer roles has lessened the utility of traditional models of media representation analysis, Shaw finds new insight on the edge of media consumption with the invisible, marginalized gamers who are surprising in both their numbers and their influence in mainstream gamer culture.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Critical media studies, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A Pedestal, A Table, A Love Letter: Archaeologies of Gender in Videogame History - Nooney, Laine (Game Studies, 2013)
The history of videogames has largely been imagined as a patrilineal timeline. Women, when they emerge as participants in the game industry, are typically figured as outliers, exceptions, or early exemplars of “diversity” in the game industry. Yet the common practice of “adding women on” to game history in a gesture of inclusiveness fails to critically inquire into the ways gender is an infrastructure that profoundly affects who has access to what kinds of historical possibilities at a specific moment in time and space. This contribution aims to shift the relevant question from “Where are women in game history?” to “Why are they there in the way that they are?” To do so, the essay strategically deploys Sierra On-Line co-founder and lead designer Roberta Williams as an exceptional case study on the problem of gender in videogame history. Drawing from both media archaeology and feminist cultural studies, this contribution first outlines the function Roberta Williams serves as a gendered subject of game history. The remainder of the essay is organized as three short, non-chronological vignettes about specific objects and practices in the biography of Roberta Williams. Attention to the contextual specificity of Roberta Williams and her historical moment produces an alternative genealogy for gaming centered around relations of intimacy and labor in domestic space. Rather than producing a chronology, the method of this essay illustrates a historical critique by sketching a contour that unsettles the presumptive logic of what we must account for when we write about the objects and subjects of game history.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

What's in a Game? Race, Gender, and LGB Representation in Video Games - Wilberg, Heather (Roosevelt University, 2011)
Though research examining violence in video games (VGs) and its potential real-world effects has been a target of academic attention, content analysis of demographical marginalization in VGs has not been as prolific. What little research there is reveals a pronounced absence and stereotyping of women and racial or ethnic minorities but ignores queer content altogether. This work explores video game demographics through quantitative analysis of the demographic composition and stereotyping of characters from 30 popular VG titles. Findings of this study support that of past analyses, evidencing that the representation of women and racial minorities is both rare and stereotyped. Queer characters are also shown to be sparse and stereotyped. While past research has largely treated race and gender separately, this study shows that multiply marginalized groups, including queers, are even more underrepresented and stereotyped. The sociocultural implications of these findings are discussed and suggestions are made for future analysis and marketing.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

The U.S. Video Game Industry: Analyzing Representation of Gender and Race - Dunlop, Janet C. (International Journal of Technology and Human Interaction, 2007)
Today’s media are vast in both form and influence; however, few cultural studies scholars ad-dress the video gaming industry’s role in domestic maintenance and global imposition of U.S. hegemonic ideologies. In this study, video games are analyzed by cover art, content, and origin of production. Whether it is earning more “powers” in games such as Star Wars, or earning points to purchase more powerful artillery in Grand Theft Auto, capitalist ideology is reinforced in a subtle, entertaining fashion. This study shows that oppressive hegemonic representations of gender and race are not only present, but permeate the majority of top-selling video games. Finally, the study traces the origins of best-selling games, to reveal a virtual U.S. monopoly in the content of this formative medium.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Género, representación y nuevas tecnologías: mujeres y video en México - Pech, Cynthia (Revista mexicana de ciencias políticas y sociales, 2006)
En este artículo, se aborda la temática del video como tecnología de género. El video es el medio de creación artística que algunas mujeres están utilizando para crear lo que se puede llamar imá genes en femenino. Se hace un acercamiento al discurso feminista y los presupuestos teóricos que se han tomado para el análisis del discurso videográfico de las mujeres. Se presenta un breve análisis de los trabajos de las videastas Pola Weiss y Pilar Rodríguez.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-TV; 2-Genre et sexualité; 2-Humanités numériques; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créatrice; _Nettoyé

The “Law and Order” of Violence Against Native Women: A Native feminist Analysis of the Tribal Law and Order Act - Robertson, Kimberly (Decolonization: Indigeneity, Education & Society, 2016)
In this essay, I aim to engage the growing body of scholarship that employs Indigenous feminist theories to understand and mobilize against the sexual and gendered violence committed against Native peoples. To accomplish this, I construct a Native feminist analysis of the 2010 Tribal Law and Order Act. I posit that despite the overwhelmingly positive characterizations of the legislation as “historic” in its potential to address violence against Native women and reduce crime in Indian country, a Native feminist reading of the Tribal Law and Order Act illuminates the degree to which the Act emerges from, engages with, and advances settler colonial and heteropatriarchal logics that cause violence against Native women in the first place. I suggest that although the Act does contain measures that have the potential to alleviate the experience of violence in Native women’s lives, it also diminishes tribal sovereignty, perpetuates the ongoing encroachment of tribal jurisdiction, regulates the boundaries of Native identity, and limits our ability to envision and enact practices of decolonization.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

“I Want to Call Their Names in Resistance”: Writing Aboriginal Women into Canadian Art History. - Farrell Racette, Sherry (Rethinking Professionalism: Essays on Women and Art in Canada, 1850-1970, 2012)
As bell hooks points out in “Aesthetic Inheritances: History Worked by Hand,” writing an inclusive art history is no easy task. Until very recently, Aboriginal women have been written out of Canadian art history, or rather art history has been written around us. How do we write ourselves in? It falls far beyond simple insertion; the erasures are far too deep. Insertion presumes a simple forgetfulness, an oversight, a neglecting of the obvious. Insertion assumes a presence. It implies a shared mode of history, a common belonging to a collective archive, and an agreed-upon understanding of what it means to be an artist. Beyond the important considerations of race, gender, culture, and social class, our distinct legal status in Canada must be acknowledged. This was particularly true for women artists working between 1880 and 1970. For much of the time period under consideration, First Nations communities lived under a profoundly restrictive regime of colonial power. Relationships between First Nations people and the Canadian state have been defined by the Indian Act, a piece of legislation enacted in 1876 and surviving, through many amendments and revisions, until the present time.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art in our Lives native Women Artists in Dialogue - Chavez Lamar, Cynthia; Farrell Racette, Sherry; Evans, Lara (School for Advanced Research Press, 2010)
The culmination of three seminars at SAR's Indian Arts Research Center (IARC) that brought together Native women artists to discuss the balancing of their art practice with the myriad roles, responsibilities, and commitments they have. The artworks were diverse in media and content and are featured in the plates section of this volume, along with the artist statements that accompanied the pieces in the exhibit. The chapters reflect some of the seminars emerging themes: gender, home/crossing, and art as healing/art as struggle
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé